Comparative analysis of different methods for evaluating quality of Quercus ilex seedlings inoculated with Tuber melanosporum - Andres-Alpuente, Antonio; Sanchez, Sergio; Martin, Maria; Javier Aguirre, Angel; Barriuso, Juan J. (MYCORRHIZA, 2014)
The quality of seedlings colonized by Tuber melanosporum is one of the main factors that contributes to the success or failure of a truffle crop. Truffle cultivation has quickly grown in European countries and elsewhere, so a commonly shared seedling evaluation method is needed. Five evaluation methods are currently published in the literature: three are used in Spain and two in France and Italy. Although all estimate the percentage colonization by T. melanosporum mycorrhizae, they do it in different ways. Two methods also estimate total number of mycorrhizae per seedling. Most are destructive. In this work, ten batches of holm oak seedlings inoculated with T. melanosporum from two different nurseries were evaluated by means of the five methods noted above. Some similarity was detected between the percentages of T. melanosporum mycorrhizae estimated by each method but not in their ability to assess the suitability of each batch. We discuss the advantages and disadvantages for each method and suggest approaches to reach consensus within the truffle culture industry for certifying mycorrhizal colonization by T. melanosporum and seedling quality.
The following values have no corresponding Zotero field: pub-location: 233 SPRING ST, NEW YORK, NY 10013 USA publisher: SPRINGER
Keywords: Black truffle; Certification; Holm oak; Mycorrhization; Nurseries; Truffle culture

Drought stress does not protect Quercus ilex L. from ozone effects: results from a comparative study of two subspecies differing in ozone sensitivity - Alonso, R; Elvira, S; González-Fernández, I; Calvete, H; García-Gómez, H; Bermejo, V (Plant Biology, 2014)
Long-term effects of ozone (O3) exposure and drought stress were assessed on two subspecies of Quercus ilex: ssp. ilex and ssp. ballota. Two-year-old seedlings were continuously exposed for 26 months in open-top chambers to three O3 treatments: charcoal filtered air, non-filtered air and non-filtered air supplemented with 40 nl·l−1 O3. Additionally, two irrigation regimes were adopted: half of the plants were well-watered and the others received half of the water supplied to control plants. Growth, shoot water potential and gas exchange rates were assessed seasonally, and biomass accumulation was determined at the end of the experiment. Drought stress caused higher reductions of gas exchange, growth and biomass accumulation than O3 exposure in both subspecies. The combination of O3 and drought stress caused further decreases of accumulated aboveground biomass but no additive effects were observed on gas exchange rates or root biomass. Thus, drought stress did not protect Q. ilex from O3 effects on biomass when the response of the whole plant was considered. Q. ilex ssp. ballota was more sensitive to O3 and ssp. ilex was more affected by drought stress. The different O3 sensitivity was not only related to pollutant uptake but also to the ability of plants for resource acquisition and allocation. Based on biomass dose–response functions, Q. ilex is more resistant to O3 than other European evergreen tree species, however, O3 represents an additional stress factor that might be impairing plant ability to withstand current and future climate change.
Keywords: evergreen broadleaf mediterranean; Evergreen broadleaf Mediterranean vegetation; Gas exchange; Growth; Holm oak; ozone response functions; Vegetation

Effects of human disturbance on nest placement of the woodpigeon (Columba palumbus): a case study from the Middle Atlas, Morocco. - Hanane, Saâd (Integrative zoology, 2014)
The woodpigeon (Columba palumbus) is a common and widespread bird in Morocco (North Africa). I examined, over 2 years (2010 and 2011), the breeding density and nest placement of this game species in relation to nest site habitat and degree of human disturbance. The study area was in the Middle Atlas Tighboula mountain forest, Morocco, in a disturbed and an undisturbed site. Using data collected in the 2 study sites, I aimed to identify the factors influencing the placement of nests within holm oak trees (Quercus rotundifolia) and their densities. I found that habitat structures, influenced by grazing disturbance, have affected nesting density and the location of nests of this species. Woodpigeons place their nests in a higher position (3.42 ± 0.19 m) when disturbance intensity is high and lower (1.68 ± 0.1 m) when disturbance intensity is low, and show higher nesting density in less disturbed zone (3.1 ± 0.4 nests/ha) than in highly disturbed zones (1.4 ± 0.2 nests/ha). Grazing disturbance could pose a threat to population persistence at a broader scale and could potentially reduce the abundance of this species by altering the composition and the structure of the forest nesting habitat. Further multi-scale studies are needed to assess the effects of different levels of grazing disturbance on woodpigeon nest density and placement, and to enhance our knowledge of the breeding behavior of this game species under variable environments.
Keywords: breeding density; columba palumbus; Holm oak; middle atlas; Morocco; nest location; woodpigeon

Light transmissivity of tube shelters affects root growth and biomass allocation of Quercus ilex L. and Pinus halepensis Mill - de Castro, Alberto Vázquez; Oliet, Juan A.; Puértolas, Jaime; Jacobs, Douglass F.; Puértolas, Jaime; Jacobs, Douglass F. (ANNALS OF FOREST SCIENCE, 2014)
Context Tube shelters have been shown to enhance field performance of several Mediterranean species, but responses of newly planted seedlings to the microenvironment induced by shelter walls with different light transmissivity are still poorly documented. Aims We studied effects of a range of shelters with varying light transmissivity on post-planting seedling responses during the wet season establishment phase for two Mediterranean trees of contrasting functional ecology. Methods Root growth, biomass allocation, water potential, and chlorophyll fluorescence of Quercus ilex and Pinus halepensis seedlings were evaluated across shelters varying in light transmissivity (80, 40, 20, and 10 % plus a mesh shelter) with irrigation. Results Plants in dark tubes (20 and 10 % light transmissivity) had less above-and belowground growth and more than two times greater leaf to protruding roots mass ratio, with shoot growth response of Q. ilex being less plastic. Ratio of leaf area/protruding roots area decreased when light transmissivity increased, although no differences were found at >= 40 % transmissivity. Xylem water potential indicated lack of water stress, and high maximum photosynthetic efficiency (F-v/F-m) values show no photoinhibition symptoms irrespective of light transmissivity. Conclusion Shelter transmissivity >= 40 % promotes rapid and vigorous root growth immediately after planting for these species. This minimum transmissivity should be considered as a target when designing shelters to help root development and improve water balance of Mediterranean seedlings.
Keywords: Aleppo pine; chlorophyll fluorescence; Forest restoration; Holm oak; Light ambient response; Mediterranean climate; Transplanting performance; Treeshelters

PAHs in decaying Quercus ilex leaf litter: Mutual effects on litter decomposition and PAH dynamics - De Nicola, F; Baldantoni, D; Alfani, a (Chemosphere, 2014)
The investigation of the relationships between litter decomposition and polycyclic aromatic hydrocarbons (PAHs) is important to shed light not only on the effects of these pollutants on fundamental ecosystem processes, such as litter decomposition, but also on the degradation of these pollutants by soil microbial community. This allows to understand the effect of atmospheric PAH contamination on soil PAH content via litterfall. At this aim, we studied mass and PAH dynamics of Quercus ilex leaf litters collected from urban, industrial and remote sites, incubated in mesocosms under controlled conditions for 361d. The results highlighted a litter decomposition rate of leaves sampled in urban>industrial>remote sites; the faster decomposition of litter of the urban site is also related to the low C/N ratio of the leaves. The PAHs showed concentrations at the beginning of the incubation of 887, 650 and 143ngg−1d.w., respectively in leaf litters from urban, industrial and remote sites. The PAHs in litter decreased along the time, with the same trend observed for mass litter, showing the highest decrease at 361d for the urban leaf litter. Anyway, PAH dynamics in all the litters exhibited two phases of loss, separated by a PAH increase observed at 246d and mainly linked to benzo[e]pyrene.
Keywords: C/N ratio; decomposition; Holm oak; Litter bags; Litter PAH contamination

Dampening effects of long-term experimental drought on growth and mortality rates of a Holm oak forest - Barbeta, Adrià; Ogaya, Romà; Penuelas, Josep (GLOBAL CHANGE BIOLOGY, 2013)
Forests respond to increasing intensities and frequencies of drought by reducing growth and with higher tree mortality rates. Little is known, however, about the long-term consequences of generally drier conditions and more frequent extreme droughts. A Holm oak forest was exposed to experimental rainfall manipulation for 13years to study the effect of increasing drought on growth and mortality of the dominant species Quercus ilex, Phillyrea latifolia, and Arbutus unedo. The drought treatment reduced stem growth of A. unedo (-66.5%) and Q. ilex (-17.5%), whereas P. latifolia remained unaffected. Higher stem mortality rates were noticeable in Q. ilex (+42.3%), but not in the other two species. Stem growth was a function of the drought index of early spring in the three species. Stem mortality rates depended on the drought index of winter and spring for Q. ilex and in spring and summer for P. latifolia, but showed no relation to climate in A. unedo. Following a long and intense drought (2005-2006), stem growth of Q. ilex and P. latifolia increased, whereas it decreased in A. unedo. Q. ilex also enhanced its survival after this period. Furthermore, the effect of drought treatment on stem growth in Q. ilex and A. unedo was attenuated as the study progressed. These results highlight the different vulnerabilities of Mediterranean species to more frequent and intense droughts, which may lead to partial species substitution and changes in forest structure and thus in carbon uptake. The response to drought, however, changed over time. Decreased intra- and interspecific competition after extreme events with high mortality, together with probable morphological and physiological acclimation to drought during the study period, may, at least in the short term, buffer forests against drier conditions. The long-term effects of drought consequently deserve more attention, because the ecosystemic responses are unlikely to be stable over time.Nontechnical summaryIn this study, we evaluate the effect of long-term (13years) experimental drought on growth and mortality rates of three forest Mediterranean species, and their response to the different intensities and durations of natural drought. We provide evidence for species-specific responses to drought, what may eventually lead to a partial community shift favoring the more drought-resistant species. However, we also report a dampening of the treatment effect on the two drought-sensitive species, which may indicate a potential adaptation to drier conditions at the ecosystem or population level. These results are thus relevant to account for the stabilizing processes that would alter the initial response of ecosystem to drought through changes in plant physiology, morphology, and demography compensation.
Keywords: acclimation; Arbutus unedo; experimental drought; global-change-type drought; Holm oak; mediterranean forest; phillyrea latifolia; Quercus ilex; tree growth; tree mortality; vegetation stabilizing processes

Foliar Symptoms Triggered by Ozone Stress in Irrigated Holm Oaks from the City of Madrid, Spain - Calderon Guerrero, Carlos; Guenthardt-Goerg, Madeleine S.; Vollenweider, Pierre (PLOS ONE, 2013)
Background: Despite abatement programs of precursors implemented in many industrialized countries, ozone remains the principal air pollutant throughout the northern hemisphere with background concentrations increasing as a consequence of economic development in former or still emerging countries and present climate change. Some of the highest ozone concentrations are measured in regions with a Mediterranean climate but the effect on the natural vegetation is alleviated by low stomatal uptake and frequent leaf xeromorphy in response to summer drought episodes characteristic of this climate. However, there is a lack of understanding of the respective role of the foliage physiology and leaf xeromorphy on the mechanistic effects of ozone in Mediterranean species. Particularly, evidence about morphological and structural changes in evergreens in response to ozone stress is missing. Results: Our study was started after observing ozone -like injury in foliage of holm oak during the assessment of air pollution mitigation by urban trees throughout the Madrid conurbation. Our objectives were to confirm the diagnosis, investigate the extent of symptoms and analyze the ecological factors contributing to ozone injury, particularly, the site water supply. Symptoms consisted of adaxial and intercostal stippling increasing with leaf age. Underlying stippling, cells in the upper mesophyll showed HR-like reactions typical of ozone stress. The surrounding cells showed further oxidative stress markers. These morphological and micromorphological markers of ozone stress were similar to those recorded in deciduous broadleaved species. However, stippling became obvious already at an AOT40 of 21 ppm.h and was primarily found at irrigated sites. Subsequent analyses showed that irrigated trees had their stomatal conductance increased and leaf life -span reduced whereas the leaf xeromorphy remained unchanged. These findings suggest a central role of water availability versus leaf xeromorphy for ozone symptom expression by cell injury in holm oak.
APSAPSThe following values have no corresponding Zotero field: pub-location: 1160 BATTERY STREET, STE 100, SAN FRANCISCO, CA 94111 USA publisher: PUBLIC LIBRARY SCIENCE
Keywords: Holm oak; Mediterranean climate; natural vegetation; Ozone; Stomatal uptake

Germination and seedling growth of holm oak (Quercus ilex L.): effects of provenance, temperature, and radicle pruning - Caliskan, Servet (IFOREST-BIOGEOSCIENCES AND FORESTRY, 2013)
This study tested acorn characteristics and the germination behavior of different provenances of Holm oak (Quercus ilex L.) and the effects of radicle clipping of germinated acorns on 1-0 year-old seedling morphology and their field performances. The results revealed that all acorn characteristics among different provenances were significant. Quercus ilex acorns germinated well at alternating temperatures of 20/10 degrees C compared to a constant 20 degrees C temperature. Radicle clipping of Q. ilex significantly increased the shoot height and root collar diameter. The average number of main roots resulting from radicle clipping was 2.8 times more than unclipped treatment. The results can contribute to nursery practices and artificial regeneration of this species.
The following values have no corresponding Zotero field: pub-location: DEPT PROD VEGETALE, VIA ATENEO LUCANO 10, POTENZA, 85100, ITALY publisher: SISEF-SOC ITALIANA SELVICOLTURA ECOL FORESTALE
Keywords: artificial regeneration; Holm oak; Quercus ilex; Radicle Pruning; seed germination; sowing

Induction of Quercus ilex L. haploid and doubled-haploid embryos from anther cultures by temperature-stress - Pintos, B; Sanchez, N; Bueno, Ma A; Ma Navarro, R; Jorrin, J; Manzanera, J A; Gomez-Garay, A (SILVAE GENETICA, 2013)
This paper describes a method to obtain haploid and doubled-haploid (DH) embryos using anther cultures of holm oak (Quercus ilex L.). The production of haploids and DH through gametic embryogenesis provides an attractive biotechnological tool for developing homozygous lines from heterozygous parents, which is important in breeding programs, as well as in genetic studies. As a consequence, protocols to produce homozygous plants have a significant impact on forest tree improvement. Anthers were subjected to different temperature treatments for embryo induction: a cold pre-treatment (4 C) from 3 to 7 days was carried out at the beginning, followed by a heat shock (33 C) from 2 to 5 days. Most anthers responding to these stress treatments contained vacuolated microspores, indicating that this developmental stage is responsive to embryogenesis induction in holm-oak microspores. In all cases, embryos grew from the interior of the anthers, breaking through the degenerating anther walls. Under these conditions, embryo formation occurred in 31 anthers between 46 and 95 days after culture initiation. Embryo analysis performed with flow-cytometry and DNA-microsatellite markers showed haploid profiles and/or spontaneous doubling of the chromosomes during early regeneration stages. This is, to our knowledge, the first published report on gametic embryogenesis in holm oak.
Keywords: anthers; Holm oak; microsatellite DNA-markers; pollen embryogenesis; Quercus ilex

Karyological and taxonomical considerations on Epipactis cupaniana sp nov (Orchidaceae) from Sicily - Brullo, Cristian; D'Emerico, Saverio; Pulvirenti, Santa (NORDIC JOURNAL OF BOTANY, 2013)
A new species of Epipactis from the Madonie massif (Sicily), E. cupaniana C. Brullo, D'Emerico and Pulv. sp. nov., is described and illustrated. It is a nemoral species, occurring in Holm oak woods, and is characterized by a diploid chromosome complement of 2n = 2x = 38. In the metaphase I, the mother cells of the embryo sac contain 19 bivalents. With respect to morphology and karyotype structure, the new species shows a close relationships with E. helleborine and other allied species, such as E. meridionalis and E. schubertiorum, both occurring in southern Italy and Sicily. However, several morphological features, chromosome size, and differences in the heterochromatin distribution allow for a clear distinction between E. cupaniana and the above-mentioned species.
APSAPSThe following values have no corresponding Zotero field: pub-location: 111 RIVER ST, HOBOKEN 07030-5774, NJ USA publisher: WILEY-BLACKWELL
Keywords: APS; embryo; Epicaptis cupaniana; Holm oak; karyotype structure; Sicily; Wood

Mark–recapture of Cerambyx welensii in dehesa woodlands: dispersal behaviour, population density, and mass trapping efficiency with low trap densities - Torres-Vila, Luis M.; Sánchez-González, Álvaro; Merino-Martínez, Jesús; Ponce-Escudero, Francisco; Conejo-Rodríguez, Yolanda; Martín-Vertedor, Daniel; Ferrero-García, Juan J. (Entomologia Experimentalis et Applicata, 2013)
The longhorn beetle, Cerambyx welensii Küster (Coleoptera: Cerambycidae), is an emerging pest involved in oak decline episodes in dehesa open woodlands. Larvae are xylophagous and cause considerable physiological, mechanical, and structural damages to trees. Chemical and biological control are currently unsatisfactory. Recent research has shown that mass trapping with a high density of baited traps (40 traps ha−1) could be useful to manage C. welensii populations, although such a trap density was too high to be cost-effective. In this 2-year study (2010–2011) we investigated with mark–recapture methods in a large plot (1) the flight dispersal behaviour, (2) the adult population density, and (3) the efficiency of mass trapping at two low trap densities (one or four traps ha−1). Results indicated that many adults were sedentary (60%) but flying adults displayed a strong propensity to move, both sexes dispersing on average more than 200 m and one male and one female flying at least 540 and 349 m, respectively. Recapture rates were high (0.26–0.35) and population density was estimated to be 6–22 adults ha−1 with maximum likelihood models. Trapping efficiency ranged 48–61% with no significant effect of trap density or year. We conclude that results were not satisfactory enough to recommend mass trapping with low trap densities as control method for C. welensii and that more research is still required on the technical, ecological, and behavioural factors affecting control efficiency.
From Duplicate 1 ( Mark–recapture of Cerambyx welensii in dehesa woodlands: dispersal behaviour, population density, and mass trapping efficiency with low trap densities - Torres-Vila, Luis M.; Sánchez-González, Álvaro; Merino-Martínez, Jesús; Ponce-Escudero, Francisco; Conejo-Rodríguez, Yolanda; Martín-Vertedor, Daniel; Ferrero-García, Juan J. )From Duplicate 1 ( Mark–recapture of Cerambyx welensii in dehesa woodlands: dispersal behaviour, population density, and mass trapping efficiency with low trap densities - Torres-Vila, Luis M.; Sánchez-González, Álvaro; Merino-Martínez, Jesús; Ponce-Escudero, Francisco; Conejo-Rodríguez, Yolanda; Martín-Vertedor, Daniel; Ferrero-García, Juan J. )
Keywords: cerambycidae; Coleoptera; Fagaceae; Holm oak; longhorn beetle; ml secr models; Oak decline; open woodland; pest control

Mark–recapture of Cerambyx welensii in dehesa woodlands: dispersal behaviour, population density, and mass trapping efficiency with low trap densities - Torres-Vila, Luis M; Sánchez-González, Álvaro; Merino-Martínez, Jesús; Ponce-Escudero, Francisco; Conejo-Rodríguez, Yolanda; Martín-Vertedor, Daniel; Ferrero-García, Juan J (Entomologia Experimentalis et Applicata, 2013)
The longhorn beetle, Cerambyx welensii Küster (Coleoptera: Cerambycidae), is an emerging pest involved in oak decline episodes in dehesa open woodlands. Larvae are xylophagous and cause considerable physiological, mechanical, and structural damages to trees. Chemical and biological control are currently unsatisfactory. Recent research has shown that mass trapping with a high density of baited traps (40 traps ha−1) could be useful to manage C. welensii populations, although such a trap density was too high to be cost-effective. In this 2-year study (2010–2011) we investigated with mark–recapture methods in a large plot (1) the flight dispersal behaviour, (2) the adult population density, and (3) the efficiency of mass trapping at two low trap densities (one or four traps ha−1). Results indicated that many adults were sedentary (60%) but flying adults displayed a strong propensity to move, both sexes dispersing on average more than 200 m and one male and one female flying at least 540 and 349 m, respectively. Recapture rates were high (0.26–0.35) and population density was estimated to be 6–22 adults ha−1 with maximum likelihood models. Trapping efficiency ranged 48–61% with no significant effect of trap density or year. We conclude that results were not satisfactory enough to recommend mass trapping with low trap densities as control method for C. welensii and that more research is still required on the technical, ecological, and behavioural factors affecting control efficiency.
From Duplicate 1 ( Mark–recapture of Cerambyx welensii in dehesa woodlands: dispersal behaviour, population density, and mass trapping efficiency with low trap densities - Torres-Vila, Luis M.; Sánchez-González, Álvaro; Merino-Martínez, Jesús; Ponce-Escudero, Francisco; Conejo-Rodríguez, Yolanda; Martín-Vertedor, Daniel; Ferrero-García, Juan J. )
Keywords: cerambycidae; Coleoptera; Fagaceae; Holm oak; longhorn beetle; ml secr models; Oak decline; open woodland; pest control

Quercus ilex L. as bioaccumulator for heavy metals in urban areas: Effectiveness of leaf washing with distilled water and considerations on the trees distance from traffic - Ugolini, Francesca; Tognetti, Roberto; Raschi, Antonio; Bacci, Laura (Urban Forestry & Urban Greening, 2013)
In recent years the use of plants as bioaccumulators or bioindicators has increased because enable the prediction of pollution for monitoring purposes, even in urban environments where traffic is a major source of heavy metals pollution. In this study we hypothesized holm oak (Quercus ilex L.) a valid trapping species for heavy metals. We also hypothesized that metals capture capacity by deposition on the crown is connected to the surrounding environmental characteristics and the distance of trees from the source of pollution. The study was conducted in the city of Florence. Holm oaks were selected in different sites near to heavy traffic roads. Concentrations of Zn, Pb, Cd, Cu, Fe, Mn, Cr, and Ba were analyzed through two methods: leaf washing with distilled water and leaf unwashing. One-year-old leaves (new leaves) were also compared with previous-year leaves (old leaves). Our results demonstrated the good capacity of this species to capture heavy metals (Pb, Fe, Mn, Cr, and Ba), particularly due to the presence of old leaves, which enhance the crown deposition surface. Washing was effective and it allowed testing the behaviour with regard to microelements: new leaves showed high Cu concentration, while old leaves had high Pb concentration. The dispersion of metals through the atmosphere was assessed through regression analysis, in two comparable gardens: leaves at farther distance from the traffic were richer in Zn, Pb, Mn, and Ba. The physical context of the surrounding environment was probably altering the distribution of heavy metals as barriers to dispersion, which can reach tens of metres from the source of pollution. Therefore, this work suggests that wind modelling and trees distribution and characteristics should be taken into consideration to evaluate the pollutants dispersion, especially for planning of recreational urban green areas.
Keywords: Deposition; Heavy metals; Holm oak; Internal concentration; Traffic pollution; Urban environment

Quercus ilex L. as bioaccumulator for heavy metals in urban areas: Effectiveness of leaf washing with distilled water and considerations on the trees distance from traffic - Ugolini, Francesca; Tognetti, Roberto; Raschi, Antonio; Bacci, Laura (Urban Forestry & Urban Greening, 2013)
In recent years the use of plants as bioaccumulators or bioindicators has increased because enable the prediction of pollution for monitoring purposes, even in urban environments where traffic is a major source of heavy metals pollution. In this study we hypothesized holm oak (Quercus ilex L.) a valid trapping species for heavy metals. We also hypothesized that metals capture capacity by deposition on the crown is connected to the surrounding environmental characteristics and the distance of trees from the source of pollution. The study was conducted in the city of Florence. Holm oaks were selected in different sites near to heavy traffic roads. Concentrations of Zn, Pb, Cd, Cu, Fe, Mn, Cr, and Ba were analyzed through two methods: leaf washing with distilled water and leaf unwashing. One-year-old leaves (new leaves) were also compared with previous-year leaves (old leaves). Our results demonstrated the good capacity of this species to capture heavy metals (Pb, Fe, Mn, Cr, and Ba), particularly due to the presence of old leaves, which enhance the crown deposition surface. Washing was effective and it allowed testing the behaviour with regard to microelements: new leaves showed high Cu concentration, while old leaves had high Pb concentration. The dispersion of metals through the atmosphere was assessed through regression analysis, in two comparable gardens: leaves at farther distance from the traffic were richer in Zn, Pb, Mn, and Ba. The physical context of the surrounding environment was probably altering the distribution of heavy metals as barriers to dispersion, which can reach tens of metres from the source of pollution. Therefore, this work suggests that wind modelling and trees distribution and characteristics should be taken into consideration to evaluate the pollutants dispersion, especially for planning of recreational urban green areas.
The following values have no corresponding Zotero field: publisher: Elsevier GmbH.
Keywords: Deposition; Heavy metals; Holm oak; Internal concentration; Traffic pollution; Urban environment

Ranges of nutrient concentrations in Quercus ilex leaves at natural and urban sites - Maisto, Giulia; Baldantoni, Daniela; De Marco, Anna; Alfani, Anna; De Santo, Amalia Virzo (JOURNAL OF PLANT NUTRITION AND SOIL SCIENCE, 2013)
The leaf nutrient concentrations and the N-to-nutrient ratios were analyzed to evaluate the nutritional status of holm oaks (Quercus ilex L.) experiencing various anthropogenic pressures. Leaves (1 year old) of Q. ilex and surface soil (0-5cm) surrounding the trees were collected at seven natural and seven urban sites in Campania Region (Southern Italy) and analyzed for the concentrations of macro (C, N, P, S) and micronutrients (Mn, K, Na, Cu, Mg, Ca, Fe, Zn). The available soil fraction of micronutrients was also evaluated. The nutrients showed different concentration ranges for the natural and the urban sites in the soil (total and available) and in the leaves, that we reported separately. Organic-matter content and macronutrient concentrations were higher in the natural soils, while the highest leaf N, S, and P concentrations were found at some urban sites. Concentrations of Cu, Na and Zn both in leaves and soil, and Mg and Fe in leaves from the urban sites appeared to be affected by air depositions. Manganese was the only micronutrient to show higher concentrations at the natural than at the urban sites, both in soil and leaves. For this nutrient, in addition, a relationship between leaf and available soil concentrations was found at the natural sites. The ratios between the concentrations of N and each studied nutrient in the leaves highlighted a different nutritional status between the plants from the natural and urban sites.
Keywords: Campania Region; Holm oak; leaf N-to-nutrient ratios; southern italy; total and available soil nutrient concentrations

Development of Quercus ilex plantations is related to soil phosphorus availability on shallow calcareous soils - Pascual, S; Olarieta, J R; Rodríguez-Ochoa, R (New Forests, 2012)
The objective of this study is to analyse the performance of Quercus ilex plantations established under semiarid conditions on different soils formed on calcareous and gypsiferous parent material. We studied eighteen 300 m 2 plots in which 1 year-old seedlings had been planted after subsoiling on the contour. Plots were stratiﬁed according to aspect (north and south) and previous land use/parent material: shrubland on limestone (LM-SH), shrubland on gypsum rock (GY-SH), and cropland on colluvium (CO-AG). Soils developed on limestone and colluvium had average rooting depths of 27 and 37 cm, respectively, and mean concentrations of active lime and phosphorus (P) of 130 and 190 mg g -1 and 10 and 19 mg kg -1 , respectively. Soils developed on gypsum had a mean rooting depth of 26 cm, and a mean gypsum concentration of 73 %. Height and diameter of trees varied signiﬁcantly according to parent material/previous land use but not to slope aspect. Mean height and diameter of trees were signiﬁcantly higher in CO-AG plots than in LM-SH and GY-SH plots. Soil P and depth were the main variables explaining differences in dominant height across all 18 plots. In CO-AG plots mean height was negatively related to soil pH but positively related to soil P concentration. In LM-SH plots, mean diameter and height were negatively related to active lime concentration. This study suggests that soil P is a major determinant of holm oak performance in shallow calcareous soils and highlights the importance of conducting detailed soil studies in order to assess the viability of plantations with this species.
Keywords: Active lime; Afforestation; Gypsum; Holm oak; Mediterranean; Semiarid areas

Manipulation of VOC emissions with methyl jasmonate and carrageenan in the evergreen conifer Pinus sylvestris and evergreen broadleaf Quercus ilex - Semiz, G; Blande, J D; Heijari, J; Işık, K; Niinemets, Ü; Holopainen, J K (Plant Biology, 2012)
Plant defence can be induced by exposing plants to the plant hormone jasmonic acid (JA) or its volatile ester, methyl jasmonate (MeJA). Carrageenans (Carr) – sulphated d-galactans extracted from red algae – can also induce plant defences. In this study, the effects of exogenous MeJA and Carr application (concentration 300 and 12.7 μmol, respectively) on volatile emissions from two widespread evergreen woody species, Pinus sylvestris (nine Turkish and one Finnish provenance) and Quercus ilex (Italian provenance) were investigated. We collected headspace samples from seedlings and analysed the quality and quantity of volatile compounds emitted by treated and control plants. In total, 19 monoterpenes, 10 sesquiterpenes, 10 green leaf volatiles (GLVs) and two aromatic compounds were emitted by P. sylvestris from all the provenances studied. Foliar MeJA application clearly affected the volatile profiles of trees from all the provenances. Effects of Carr were genotype specific. In Q. ilex, emissions of sesquiterpenes, GLVs and the homoterpene (E)-DMNT were all induced by MeJA application. However, emissions of most constitutively emitted monoterpenes were significantly reduced. Carr application also led to a significant reduction in monoterpene emissions, but without corresponding increases in other emissions. Our results indicate that exogenously applied MeJA and Carr can both significantly modify the volatile profiles of P. sylvestris and Q. ilex, but also that there are important provenance- and species-specific differences in the overall degree of elicitation and compositions of elicited compounds.
Keywords: Algal polysaccharide; elicitor; Holm oak; inducible volatiles; scots pine; terpenes

A model to account for variations in production in southern Spain - García-mozo, Herminia; Dominguez-vilches, Eugenio; Galán, Carmen (Annals of Agricultural and Environmental Medicine, 2012)
One of the characteristics of holm-oak acorn production is its high variability among individuals and years. To examine the main causes of this fact, a study was conducted from 1998-2010 in a natural area of holm-oak in southern Spain, where floral phenology, fruit production, fruit size, airborne pollen emission and meteorology factors were analyzed with the ultimate aim of developing a model for forecasting holm-oak yield. Pollen emission during flowering season was the main factor determining the final acorn harvest, but also some meteorological variables played an important role in explaining acorn crop variations, especially humidity and temperature during the months of April and September. The reliability of the proposed model was externally validated using data not included in its construction; validation yielded acceptable results, with a minimum error of estimation. Our results appear to be very useful for planning cropping and pig feeding strategies. Further research could extend the use of airborne pollen counts in forest studies relating to anemophilous species, in order to optimize agricultural policies.
Keywords: acorn production; Aerobiology; Holm oak; model; oak forest; Phenology; pollen; quercus ilex subsp. ballota

Observations of the uptake of carbonyl sulfide (COS) by trees under elevated atmospheric carbon dioxide concentrations - Sandoval-Soto, L; Kesselmeier, M; Schmitt, V; Wild, A; Kesselmeier, J (Biogeosciences, 2012)
. Global change forces ecosystems to adapt to elevated atmospheric concentrations of carbon dioxide (CO2). We understand that carbonyl sulﬁde (COS), a trace gas which is involved in building up the stratospheric sulfate aerosol layer, is taken up by vegetation with the same triad of the enzymes which are metabolizing CO2, i.e. ribulose-1,5- bisphosphate carboxylase/oxygenase (Rubisco), phosphoenolpyruvate carboxylase (PEP-Co) and carbonic anhydrase (CA). Therefore, we discuss a physiological/biochemical acclimation of these enzymes affecting the sink strength of vegetation for COS. We investigated the acclimation of two European tree species, Fagus sylvatica and Quercus ilex, grown inside chambers under elevated CO2, and determined the exchange characteristics and the content of CA after a 1–2 yr period of acclimation from 350 ppm to 800 ppm CO2. We demonstrate that a compensation point, by deﬁnition, does not exist. Instead, we propose to discuss a point of uptake afﬁnity (PUA). The results indicate that such a PUA, the CA activity and the deposition velocities may change and may cause a decrease of the COS uptake by plant ecosystems, at least as long as the enzyme acclimation to CO2 is not surpassed by an increase of atmospheric COS. As a consequence, the atmospheric COS level may rise causing an increase of the radiative forcing in the troposphere. However, this increase is counterbalanced by the stronger input of this trace gas into the stratosphere causing a stronger energy re- ﬂection by the stratospheric sulfur aerosol into space (Bruhl ¨ et al., 2012). These data are very preliminary but may trigger a discussion on COS uptake acclimation to foster measurements with modern analytical instruments.
Keywords: beech (voyant); COS uptake; Elevated CO2; Holm oak

Photoprotection mechanisms in Quercus ilex under contrasting climatic conditions - Camarero, Jesús Julio; Olano, José Miguel; Arroyo Alfaro, Sandra Jackeline; Fernández-Marín, Beatriz; Becerril, José Maria; García-Plazaola, José Ignacio (Flora - Morphology, Distribution, Functional Ecology of Plants, 2012)
Acclimation to local conditions may produce adaptive responses in plants subjected to diverse climatic stresses. However, it has not been assessed how local adaptation and phenotypic plasticity contribute to photoprotection mechanisms in response to contrasting climatic conditions in Mediterranean tree species. We analyzed photoprotectionmechanisms inmature trees oftheMediterranean evergreen oak Quercus ilex at three sites with contrasting climatic conditions, i.e. xeric, continental and mesic sites. We studied morphological and physiological parameters indicative of photoprotection in adult trees in the ﬁeld. In order to establish whether these parameters were genetically determined we compared adults with seedlings germinated from acorns of the three sites and grown under common greenhouse conditions. In the ﬁeld we found no signiﬁcant differences in most of the physiological parameters in summer, but in winter the adulttrees fromthe continental site were photoinhibited. In contrast,there were signiﬁcant differences between seedlings in most photoprotective parameters evaluated. Morphological traits such as trichome density and leaf reﬂectance differed between populations, both in ﬁeld-grown trees and in greenhouse-grown seedlings, being higher in all cases in plants from the xeric site than elsewhere. Our ﬁndings suggest the existence of constitutive differences in leaf photoprotection mechanisms among Q. ilex populations. These divergences may represent an inherent source for more stress tolerant ecotypes in the face of changing climatic conditions.
The following values have no corresponding Zotero field: publisher: Elsevier GmbH.
Keywords: ecotypes; Holm oak; Mediterranean; photoprotection; Trichomes

Preliminary Investigation of LED Lighting as Growth Light for Seedlings from Different Tree Species in Growth Chambers - ASTOLFI, Stefania; MARIANELLO, Chiara; GREGO, Stefano; BELLAROSA, Rosanna (Notulae Botanicae Horti Agrobotanici Cluj-Napoca, 2012)
The influence of light quality on growth and metabolic activity during pre-cultivation (in miniplug containers) of beech (Fagus sylvatica L.), holm oak (Quercus ilex L.) and wild cherry (Prunus avium) plants was investigated. Seedlings were grown in a growth chamber for a month under light-emitting diode (LED) light or fluorescent light. The LED lamps (Valoya) used in this study emitted a continuous spectrum thanks to a mixture of blue, green, red and far-red LEDs. Our results showed that plant response to light quality seems to be related to the plant species. In particular, in beech seedlings fresh and dry weight, shoot height and leaf area were greatest when plants were cultured under LED light, and lowest under fluorescent lamps. Furthermore, we found that LED-induced reduction of chlorophyll contents in beech and holm oak leaves resulted in an increase of the carboxylase capacity of Rubisco in the same plant species suggesting an improvement of light-use-efficiency in these plants. These results indicate that LED light may be suitable for the culture of plants in tightly controlled environments. The comparison of malondialdehyde levels between LED and fluorescent grown plants strongly supports this idea.
Keywords: beech; glutamine synthetase; Holm oak; light; lipid peroxidation; Rubisco; wild cherry

Responses of a scatter-hoarding rodent to seed morphology: links between seed choices and seed variability - Muñoz, Alberto; Bonal, Raul; Espelta, Josep Maria (Animal Behaviour, 2012)
Seed preferences of scatter-hoarding granivores may inﬂuence the evolution of seed traits in plants. However, there is little evidence linking the granivores’ responses to speciﬁc seed traits to the variability of seeds in a single plant species. This information is essential for understanding how the decisions of granivores can shape plant life histories. We analysed how seed morphology (size and shape) of the Holm oak, Quercus ilex, inﬂuences seed choices of the seed-disperser, the Algerian mouse, Mus spretus. We studied the seed variability of the oak and whether the frequency of seed phenotypes matched the seed choices of the disperser. The probabilities of seed removal decreased as the seeds became larger and more bullet-shaped, so that seeds that were simultaneously large and bullet-shaped had the lowest probabilities of being dispersed. These seeds are probably refused by rodents because they impose higher handling and transport costs. The size and shape of the Holm oak seeds were highly variable between trees, but extraordinarily consistent within a single tree over different years. However, the analysis of seed variability revealed a disproportionately low frequency of large bullet-shaped phenotypes, which are those barely removed by rodents. Seed preferences of dispersers of species with high seed variability between trees can lead to differences in the chances of seeds produced by different trees being dispersed. Those seed phenotypes preferred by dispersers could make a higher contribution to the next generation, which could inﬂuence the evolution and variability of seeds in a plant species
Keywords: acorn; Algerian mouse; animal-plant interaction; handling cost; hoarding behaviour; Holm oak; Mus spretus; Quercus ilex; seed caching; small rodent

Seed storage in polyethylene bags of a recalcitrant species (Quercus ilex): analysis of some bio-energetic and oxidative parameters - Pasquini, Sergio; Mizzau, Michela; Petrussa, Elisa; Braidot, Enrico; Patui, Sonia; Gorian, Fabio; Lambardi, Maurizio; Vianello, Angelo (Acta Physiologiae Plantarum, 2012)
Some technological and physiological aspects were analysed during seed storage of holm oak (Quercus ilex L.), a typical Mediterranean recalcitrant species. Considering the mild dormancy and desiccation sensitivity of these seeds, the inﬂuence of the storage environment on viability was examined. Acorns were maintained at low temperature and at high moisture content either inside thin polyethylene bags or mixed with peat in a bin. Storage in polyethylene bags, if compared with peat treatment, maintained optimal seed quality parameters. The effects of the two treatments on some physiological parameters were analysed during 1-year seed storage. Acorns stored in a bin with peat started to germinate early and exhibited a more rapid seed deterioration caused by metabolism-linked oxidative damage. The latter phenomenon was linked to a higher respiration and H2O2 level, induction of catalase activity, as well as lowered glutathione pool and ATP content. In addition, a more oxidized redox poise was observed. On the contrary, the plastic ﬁlm of polyethylene, limiting gaseous exchanges, maintained acorn metabolic activity at low levels and allowed the accumulation of ethylene inside the storage atmosphere. These factors, inducing a dormant-like state, could have played a crucial role in prolonging seed storage.
Keywords: antioxidant; ethylene; Holm oak; storage

Susceptibility of common herbaceous crops to Phytophthora cinnamomi and its influence on Quercus root rot in rangelands - Serrano, María S; Fernández-Rebollo, Pilar; Vita, Paolo; Sánchez, M Esperanza (European Journal of Plant Pathology, 2012)
The susceptibility to Phytophthora cinnamomi of four crops (wheat, oat, vetch, and yellow lupin) commonly planted in rangeland ecosystems in southern Spain was evaluated. By means of in vitro infection experiments, the presence of the pathogen into the roots of yellow lupin (symptomatic) and vetch (asymptomatic) was observed, but never into wheat and oat roots (asymptomatic). It was also demonstrated that yellow lupin stimulated the production of zoospores of P. cinnamomi. Vetch, wheat and oat did not stimulate zoospore production. Under controlled conditions, only yellow lupin induced an increase in the number of viable chlamydospores in the soil. We concluded that the culture of wheat, oat, and vetch in rangelands did not influence the epidemiology of the Quercus root disease, even when asymptomatically-infected vetch is grown, and these crops can constitute an alternative to the culture of yellow lupin in rangeland ecosystems affected by Quercus root rot.
Keywords: Dehesa; Holm oak; oat; vetch; wheat; yellow lupin

Tree biomass and deadwood density into aged holm oak (Sardinia) and beech coppices (Tuscany) - Bertini, G.; Fabbio, G.; Piovosi, M.; Calderisi, M. (Forest@ - Rivista di Selvicoltura ed Ecologia Forestale, 2012)
Keywords: 108-129; 2011; 2012; 9; accepted; aged coppice forest; beech; bertini g; calderisi m; citation; deadwood; densità di biomassa e; fabbio g; FOREST; Holm oak; http; in toscana; invecchiati di leccio in; it; jul 21; living woody biomass; mar 19; may 07; necromassa legnosa in cedui; online 2012-05-07; piovosi m; published online; received; sardegna e di faggio; sisef; url; wood decay; www

Autumn fertilization of Quercus ilex ssp. ballota (Desf.) Samp. nursery seedlings: effects on morpho-physiology and field performance - Andivia, Enrique; FERNÁNDEZ, MANUEL; VÁZQUEZ-PIQUÉ, JAVIER (Annals of Forest Science, 2011)
& Background The Holm oak (Quercus ilex ssp. ballota [Desf.] Samp.) is an evergreen tree widely distributed in the western Mediterranean Basin. Forest restoration programs using this species have enjoyed only limited success, and knowledge concerning the effect of fertilization on plant quality and post-transplantation response is sparse. & Methods We assessed the effect of autumn fertilization using different doses of nitrogen, phosphorus, and potassium (70.0 mg N, 30.5 mg P and 58.1 mg K during the growing phase for all plants; and 30.0 vs 1.5 mg N, 13.1 vs 0.3 mg P and 24.9 vs 0.5 mg K during the hardening phase, depending on the fertilization treatment) on the seedling characteristics and field performance of Holm oak. & Results and Conclusions Autumn fertilization, especially with N, did not decrease plant quality but improved overall growth, root growth capacity, cold hardiness, and the nutritional content of nursery-grown seedlings. However, autumn fertilization had only a small effect on field performance, which was affected only by K fertilization, probably because of the adequate N and P nutrient status of all the plants and the mild weather conditions of the field plot. In our site, which had a mild winter climate, late autumn out-planting was more successful than was midwinter out-planting.
Keywords: Cold hardiness; Field performance; Holm oak; Nursery fertilization; Nutritional status

Autumn fertilization with nitrogen improves nutritional status, cold hardiness and the oxidative stress response of Holm oak (Quercus ilex ssp. ballota [Desf.] Samp) nursery seedlings - Andivia, Enrique; Márquez-García, Belén; VÁZQUEZ-PIQUÉ, JAVIER; Córdoba, Francisco; FERNÁNDEZ, MANUEL (Trees, 2011)
Holm oak (Quercus ilex ssp. ballota [Desf.] Samp) is one of the most important species in forest communities of the western Mediterranean Basin, but is very vulnerable to environmental stress during the ﬁrst years of its life. In particular, summer drought and winter frosts limit the distribution, survival, and growth of Holm oak. These two stress factors can lead to plasmolysis and/or oxidative stress. We hypothesized that autumn fertilization with nitrogen (N) can improve plant tolerance to these abiotic stress factors and improve plant quality and therefore reforestation success. A 12-week autumn application of 30 or 60 mg N (plus 70 mg N applied to both treatments during the previous 28 weeks in the nursery, i.e. 100 and 130 mg N in total, respectively) improved overall growth, root growth capacity, frost tolerance, and nutritional status of plants relative to plants given 0.0 and 1.5 mg autumnal N, and had no negative effect on seedling response to water stress. A very small increment in N doses during the autumn (1.5 vs. 0.0 mg N) improved some morphological parameters, such as stem diameter (D) and shoot dry weight, and physiological parameters, such as total antioxidant activity. The highest autumnal N dose (60 mg) increased leaf nutrient content without decreasing the concentration, but had a tendency to reduce frost tolerance relative to seedlings given a lower autumnal N dose (30 mg).
Keywords: Frost tolerance; Holm oak; Mineral nutrients; Oxidative stress; water stress

Canopy cover influence on macrofungal richness and sporocarp production in montado ecosystems - Santos-Silva, C.; Gonçalves, A.; Louro, R. (Agroforestry Systems, 2011)
In this study we aimed to ﬁnd out how macrofungi richness and sporocarp production varies in relation to both canopy cover and proximity of crown projection area, in order to discuss strategies and point out management actions that ensure macrofungal communities sustainability in montado ecosystems. The sporocarp survey was conducted once every two weeks, from October to February, between 2007 and 2009 in two representative sites of the most common (cork and holm oak) open montado ecosystems in southern Portugal. Results showed that canopy cover strongly shaped macrofungal communities composition and yield. Denser canopy cover enhanced mycorrhizal richness and reduced saprotrophic yield. Furthermore, mycorrhizal richness and yield increased with tree proximity. Finally some forest management strategies are suggested in order to enhance macrofungal richness and productivity, in montado ecosystems.
Keywords: Cork oak; crown influence; Holm oak; macrofungal communities; Mediterranean ecosystem; montado; Portugal

Effect of different storage conditions in recalcitrant seeds of holm oak (Quercus ilex L.) during germination - Pasquini, S; Braidot, E; Petrussa, E; Vianello, A (Seed Science and Technology, 2011)
The effect of three different storage treatments on holm oak (Quercus ilex L.) acorns was examined over a period of twelve months. Acorns from two seed lots were stored at 3°C with three different treatments: acorns mixed with peat inside a can with a pierced pipe through the middle, acorns mixed in moistened sand, or acorns inside polyethylene bags without medium. Samples were collected every two months and were analyzed for moisture content, germination and electrolyte leakage. Storage of acorns in polyethylene bags maintained the high seedling percentage usually observed after harvest in germination tests. The acorns stored mixed with peat or sand failed to maintain the germination vigour observed at harvest. Electrolyte leakage was significantly higher for acorns stored in peat rather than for the other two treatments. However, acorns stored in sand and in peat had a higher level of moisture content than those kept in polyethylene bags. These results suggest that storage of acorns from the recalcitrant holm oak in polyethylene bags could preserve the acorn germination over a longer period of time with respect to the usual methods.
Keywords: acorn storage conditions; electrolyte leakage; germination; Holm oak; Moisture content; recalcitrant seed (voyant)

Establishing grazing and grazing-excluded patches increases plant and invertebrate diversity in a Mediterranean oak woodland - Bugalho, Miguel N; Lecomte, Xavier; Gonçalves, Merícia; Caldeira, Maria C; Branco, Manuela (Forest Ecology and Management, 2011)
Grazing is a global, dominant land use affecting biodiversity and ecosystem processes. In Mediterranean ecosystems grazing is a major ecological and evolutionary driver but, surprisingly, there is little information on the use of grazing as a tool to manage biodiversity in these ecosystems. We conducted an experiment to assess if establishing grazing and small scale grazing-excluded areas would increase plant and invertebrate diversity in a Mediterranean evergreen oak woodland. Plant community traits were different between treatments. Biomass of herbs (176.7±18.3 gm−2 vs 100.4±10.6 gm−2) and litter (291.0±38.3 gm−2 vs 186.8±26.4 gm−2), as well as the total cover of legumes (0.83±0.05 vs 0.91±0.03) were higher, and the proportion of bare ground (0.83±0.05 vs 0.91±0.03) was lower, in ungrazed plots. There were no differences in the number of plant species between treatments. Some plant species and invertebrate taxa were recorded exclusively in grazed or ungrazed plots. Invertebrate detritivores and sap sucking insects were more abundant in ungrazed plots. Ant assemblages were functionally different between treatments: Honeydew-gatherer ants were associated with ungrazed and higher plant biomass plots, and seed-eaters as well as aggressive predator ant species were associated with grazed, open habitat, plots. Management practices that maintain grazing and small scale grazing-excluded areas can increase habitat heterogeneity and promote herbaceous plant and invertebrate diversity at the local level.
Keywords: Cork oak; Deer; Grazing management; Holm oak; Land-use; montados

Mediterranean pine and oak distribution in southern Spain: Is there a mismatch between regeneration and adult distribution? - Urbieta, Itziar R; Garcia, Luis V; Zavala, MIGUEL a; Marañón, Teodoro (Journal of Vegetation Science, 2011)
Questions: What is the current distribution of pine and oak species along environmental gradients in southern Spain? Do pine and oak regeneration niches differ from the environmental niches of adults? Is oak species regeneration favoured under the canopy of pine forests? Location: Forest areas of Andalusia (∼87 600 km2, southern Spain). Methods: We compiled extensive forest inventory data to explore differences in abundance (basal area, m2 ha−1) patterns of adults (dbh >7.4 cm) and regeneration (dbh ≤7.4 cm) of five pine and five oak species. Canonical correspondence analysis (CCA) and generalized linear models were applied to explore species–environment relationships along climatic, edaphic, topographic and fire-frequency gradients. Results: Both pines and oaks segregated along complex environmental gradients, with pines generally dominating in more severe (colder and drier) environments, while oaks dominated in milder, wetter winter areas. In 40-55% of mature pine stands there was a lack of regeneration in the understorey, while in two oak species (Q. suber and Q. canariensis) 70% of stands did not show regeneration. Pine recruits were found at a higher frequency and abundance under the canopy of their congeners, whereas some oaks (Q. ilex) had greater regeneration under mixed pine–oak canopies. Conclusions: Climatic limitations and soil properties partly explained the regional distribution of pines and oaks. We found evidence for an upward shift of Q. ilex recruits towards areas with colder conditions in pine forests, which could be explained by a possible facilitative effect of the pine canopy on seedling establishment.
Keywords: Distribution range; Holm oak; mediterranean forest; Niche expansion; Pinus spp.; Quercus spp.; regeneration dynamics

Some propagation methods for cloning holm oak (Quercus ilex L.) plants - Liñán, Juana; Cantos, Manuel; Troncoso, Javier; García, José L; Fernández, Antonio; Troncoso, Antonio (Central European Journal of Biology, 2011)
Holm oak (Quercus ilex L.), a typical evergreen tree of the Mediterranean area, is very important due to its ecological and economical values. Propagation of this species is extremely difficult and traditionally carried out only by seed germination. In this work, mature acorns were germinated in vitro and in peat substrate in aseptic and non-aseptic conditions. Explants from the seedlings obtained were propagated in vitro in WPM plus 4 µM BA. Plant regeneration was achieved from hypocotyls and root segments cultured in vitro on modified Gamborg medium plus 20 µM BA and 20 µM NAA. 13.8% of the hypocotyls and approximately 30% of the root segments developed both shoots and roots after 30 days of culture. Rooting of stem segments was obtained both in vitro and ex vitro by basal dipping in IBA solutions. Within ex vitro rooting, mother plant age had major influence on the percentage of rooting of the cuttings as the younger plants showed higher ability to root. In this way, Q. ilex plants could be propagated and cloned. The procedure described here would be a very useful tool for breeding programs since vegetative propagation of selected individuals can be achieved.
Keywords: Holm oak; in vitro; plant regeneration; Quercus ilex; rooting; seed germination

Some propagation methods for cloning holm oak (Quercus ilex L.) plants - Liñán, Juana; Cantos, Manuel; Troncoso, Javier; García, José L.; Fernández, Antonio; Troncoso, Antonio (Central European Journal of Biology, 2011)
Holm oak (Quercus ilex L.), a typical evergreen tree of the Mediterranean area, is very important due to its ecological and economical values. Propagation of this species is extremely difficult and traditionally carried out only by seed germination. In this work, mature acorns were germinated in vitro and in peat substrate in aseptic and non-aseptic conditions. Explants from the seedlings obtained were propagated in vitro in WPM plus 4 µM BA. Plant regeneration was achieved from hypocotyls and root segments cultured in vitro on modified Gamborg medium plus 20 µM BA and 20 µM NAA. 13.8% of the hypocotyls and approximately 30% of the root segments developed both shoots and roots after 30 days of culture. Rooting of stem segments was obtained both in vitro and ex vitro by basal dipping in IBA solutions. Within ex vitro rooting, mother plant age had major influence on the percentage of rooting of the cuttings as the younger plants showed higher ability to root. In this way, Q. ilex plants could be propagated and cloned. The procedure described here would be a very useful tool for breeding programs since vegetative propagation of selected individuals can be achieved.
Keywords: Holm oak; in vitro; plant regeneration; Quercus ilex; rooting; seed germination

Two provenances of Quercus ilex ssp. ballota (Desf) Samp. nursery seedlings have different response to frost tolerance and autumn fertilization - Andivia, Enrique; FERNÁNDEZ, MANUEL; VÁZQUEZ-PIQUÉ, JAVIER; Alejano, Reyes (European Journal of Forest Research, 2011)
Despite evidences that Holm oak has a high plasticity and great adaptability, there is limited or contradictory knowledge of the morphological and physiological variability of this species. Holm oak has been widely used for reforestation projects in Mediterranean areas, but has frequently shown poor ﬁeld performance. We hypothesized that Holm oak has inter-population differences in physiological responses to abiotic stressors that could affect reforestation success. The inﬂuence of nursery culture on the characteristics of Holm oaks from different provenances has not been explored in depth. Thus, we studied the effect of nursery autumn fertilization on morphological traits, frost tolerance, root growth potential, and nutritional status of two Spanish provenances of Holm oak, La Alcarria (a region with inland Mediterranean climate) and Sierra Morena Occidental (a region with a warm coastal Mediterranean climate). There were signiﬁcant differences between the provenances in frost tolerance, biomass allocation, and leaf nutrient content, suggesting a role of genetic factors. The leaves of seedlings from La Alcarria had less visual damage at -12C than seedlings from the warmer provenance (45% vs. 92%). Seedlings from La Alcarria, compared to those from Sierra Morena, had higher leaf P concentration (0.17% vs. 0.15%), greater stem diameter (3.1 mm vs. 2.7 mm), lower shoot-to-root dry mass ratio (0.46 vs. 0.53), and lower slenderness (4.03 vs. 5.31). For both provenances, N autumn fertilization improved growth, root growth potential, cold hardiness, and nutritional status of seedlings. We suggest that forest reforestation programs should consider to a greater extent Holm oak provenances and their tolerances to different abiotic stressors.
Keywords: á autumn fertilization; á reforestation á; Adaptation; adaptation á cold hardiness; Autumn fertilization; Cold hardiness; Holm oak; holm oak á provenance; provenance; Reforestation

Vessel features of Quercus ilex L. growing under Mediterranean climate have a better climatic signal than tree-ring width - Campelo, Filipe; Nabais, Cristina; Gutiérrez, Emilia; Freitas, Helena; García-González, Ignacio (Trees, 2010)
We investigated whether vessel time series of Holm oak (Quercus ilex L.), a diffuse to semi-ring-porous species, can record a climatic signal which differs from the signal encoded in tree-ring width (TRW). The study was conducted in ten Q. ilex trees from a coppice stand in northeast Spain. Chronologies of TRW, mean vessel area (MVA) and maximum vessel area (MAX) were developed and correlated with climate data, for the period 1985–2004 (20 years). Our results indicate that vessel features contain environmental information that is different from that stored in TRW. MAX chronologies correlate better to early spring precipitation (April–May) than TRW chronologies, and so does MVA of the largest 20–25 vessels from the ﬁrst third of the ring with late spring precipitation (May–June). Also, the combination of MVA and TRW is a better predictor of summer precipitation. This explorative study clearly shows that vessel features can complement the climatic signal of TRW increasing the resolution of the climate reconstructions for the Mediterranean region.
Keywords: Dendrochronology; Holm oak; Mediterranean climate; Tree ring; Vessel features

Epigeous macrofungi of the Parque de Natureza de Noudar in Alentejo (Portugal) - Louro, R; Calado, M; Pinto, B; Santos-Silva, C (Mycotaxon, 2009)
This inventory represents the first list of the epigeous macrofungi collected in Parque de Natureza de Noudar (Barrancos, Alentejo, Portugal). Throughout 3 years 162 taxa were registered, from which 8 are new species for Portugal and 77 for Alentejo. Some of them are considered rare species whereas others have been suggested to acquire a conservation status.
Keywords: fungi; Holm oak; iberian peninsula; Mediterranean ecosystem; sporocarps

Epigeous macrofungi of the Parque de Natureza de Noudar in Alentejo (Portugal) - Louro, R.; Calado, M.; Pinto, B.; Santos-Silva, C. (Mycotaxon, 2009)
This inventory represents the first list of the epigeous macrofungi collected in Parque de Natureza de Noudar (Barrancos, Alentejo, Portugal). Throughout 3 years 162 taxa were registered, from which 8 are new species for Portugal and 77 for Alentejo. Some of them are considered rare species whereas others have been suggested to acquire a conservation status.
Keywords: fungi; Holm oak; iberian peninsula; Mediterranean ecosystem; sporocarps

Generation of a Species-Specific Look-Up Table for Fuel Moisture Content Assessment - Yebra, M.; Chuvieco, E. (Selected Topics in Applied Earth Observations and Remote Sensing, IEEE Journal of, 2009)
This study involved the generation of a species-specific Look-Up Table (LUT) for the retrieval of Fuel Moisture Content (FMC) in natural areas dominated by Quercus ilex (Holm oak). Parameter combinations observed in drying Q. ilex samples were used as inputs into the linked PROSPECT and SAILH Radiative Transfer Models (RTM) to avoid unrealistic simulated spectra in the LUT. Terra/MODIS reflectance data, extracted over five plots dominated by Q. ilex, were used to carry out the LUT inversion. This inversion was based on the search for the minimum relative root mean square error (RMSErho*) between observed and simulated reflectance found in the LUT. Different inversion options were tested in order to search for the optimal spectral sampling necessary for accurately estimating FMC. The minimum number of solutions required for the calculation of the estimated FMC was also investigated. The retrieval performance was evaluated with FMC values measured at the five study plots. The most accurate FMC estimation was obtained when using the normalized difference infrared index (NDII6 ) and selecting the ten best cases as the solution (RMSE=26.28%). Finally, a non-oak-specific LUT (generic LUT) was used in the same way to evaluate whether or not the species-specific LUT retrieved FMC more accurately. The results showed that the species-specific LUT provided more accurate FMC estimations than the generic LUT. Only when the number of solutions was higher than 35 was the accuracy of the two LUT similar. Future work will focus on the possibility of generating a LUT adapted to a wider range of species based on data extracted from field measurements and literature.
Keywords: Fuel moisture content (FMC); Holm oak; MODIS; Quercus ilex; Radiative Transfer Models (RTM)

Generation of a Species-Specific Look-Up Table for Fuel Moisture Content Assessment - Yebra, M; Chuvieco, E (Selected Topics in Applied Earth Observations and Remote Sensing, IEEE Journal of, 2009)
This study involved the generation of a species-specific Look-Up Table (LUT) for the retrieval of Fuel Moisture Content (FMC) in natural areas dominated by Quercus ilex (Holm oak). Parameter combinations observed in drying Q. ilex samples were used as inputs into the linked PROSPECT and SAILH Radiative Transfer Models (RTM) to avoid unrealistic simulated spectra in the LUT. Terra/MODIS reflectance data, extracted over five plots dominated by Q. ilex, were used to carry out the LUT inversion. This inversion was based on the search for the minimum relative root mean square error (RMSErho*) between observed and simulated reflectance found in the LUT. Different inversion options were tested in order to search for the optimal spectral sampling necessary for accurately estimating FMC. The minimum number of solutions required for the calculation of the estimated FMC was also investigated. The retrieval performance was evaluated with FMC values measured at the five study plots. The most accurate FMC estimation was obtained when using the normalized difference infrared index (NDII6 ) and selecting the ten best cases as the solution (RMSE=26.28%). Finally, a non-oak-specific LUT (generic LUT) was used in the same way to evaluate whether or not the species-specific LUT retrieved FMC more accurately. The results showed that the species-specific LUT provided more accurate FMC estimations than the generic LUT. Only when the number of solutions was higher than 35 was the accuracy of the two LUT similar. Future work will focus on the possibility of generating a LUT adapted to a wider range of species based on data extracted from field measurements and literature.
Keywords: Fuel moisture content (FMC); Holm oak; MODIS; Quercus ilex; Radiative Transfer Models (RTM)

INFLUENCIA DEL CULTIVO DE LUPINUS LUTEUS L. EN LA DENSIDAD DE INÓCULO DE PHYTOPHTHORA CINNAMOMI EN SUELOS DE DEHESA - SERRANO, M S; SÁNCHEZ, M E; DE VITA, P; CARBONERO, M D; TRAPERO, A; FERNÁNDEZ-REBOLLO, P (Actas de la XLVIII RC de la SEEP. Huesca La multifuncionalidad de los pastos: producción ganadera sostenible y gestión de los ecosistemas, 2009)
Phytophthora cinnamomi is a pathogen causing root rot in oak trees growing in dehesa sys- tems and also in yellow lupine, a common pasture crop in western Andalusia. In dehesas show- ing different situations in terms of tree decline and disease severity in the lupines, isolation and counting of colonies of P. cinnamomi from soil samples has shown the ability of the herbaceous crop to maintain or increase the inoculum density and thus may enhance oak infections. The obtained results discourage the cultivation of this legume in dehesas with known presence of the pathogen in the soil, whether the trees are suffering the root disease or not.
Keywords: decline; Holm oak; root rot; yellow lupine

INFLUENCIA DEL CULTIVO DE LUPINUS LUTEUS L. EN LA DENSIDAD DE INÓCULO DE PHYTOPHTHORA CINNAMOMI EN SUELOS DE DEHESA - Serrano, M. S.; Sanchez, M. E.; De Vita, P.; CARBONERO, M. D.; Trapero, A.; FERNÁNDEZ-REBOLLO, P. (Actas de la XLVIII RC de la SEEP. Huesca La multifuncionalidad de los pastos: producción ganadera sostenible y gestión de los ecosistemas, 2009)
Phytophthora cinnamomi is a pathogen causing root rot in oak trees growing in dehesa sys- tems and also in yellow lupine, a common pasture crop in western Andalusia. In dehesas show- ing different situations in terms of tree decline and disease severity in the lupines, isolation and counting of colonies of P. cinnamomi from soil samples has shown the ability of the herbaceous crop to maintain or increase the inoculum density and thus may enhance oak infections. The obtained results discourage the cultivation of this legume in dehesas with known presence of the pathogen in the soil, whether the trees are suffering the root disease or not.
The following values have no corresponding Zotero field: periodical: Actas de la XLVIII RC de la SEEP. Huesca La multifuncionalidad de los pastos: producción ganadera sostenible y gestión de los ecosistemas pub-location: Huesca
Keywords: decline; Holm oak; root rot; yellow lupine

Physiological responses of cork oak and holm oak to infection by fungal pathogens involved in oak decline - Linaldeddu, B. T.; Sirca, C.; Spano, D.; Franceschini, A. (Forest Pathology, 2009)
The aim of this research was to study the changes in net photosynthesis and stomatal conductance values in 3-year-old cork oak and holm oak seedlings growing in natural conditions and inoculated with Apiognomonia quercina, Biscogniauxia mediterranea, Botryosphaeria corticola and Pleurophoma cava. Throughout the 4-month experimental period, the evolution of visual external symptoms and the values of physiological variables were periodically recorded. All pathogens caused stem lesions around the infection point; however, the lesions caused by B. corticola were longer in both oak species. On cork oak seedlings, all pathogens induced a signiﬁcant and gradual reduction in net photosynthesis and stomatal conductance values, whereas other physiological disturbances were induced only by B. corticola infections on holm oak seedlings.
Keywords: Cork oak; fungal pathogens; Holm oak; physiological responses (voyant); seedlings

Seasonality of monoterpene emission potentials in Quercus ilex and Pinus pinea: Implications for regional VOC emissions modeling - KEENAN, Trevor; Niinemets, Ülo; Sabaté, Santi; Gracia, Carlos; Penuelas, Josep (Journal of Geophysical Research: Atmospheres, 2009)
VOC emissions from terrestrial ecosystems provide one of the principal controls over oxidative photochemistry in the lower atmosphere and the resulting air pollution. Such atmospheric processes have strong seasonal cycles. Although similar seasonal cycles in VOC emissions from terrestrial ecosystems have been reported, regional emissions inventories generally omit the effect of seasonality on emissions. We compiled measurement data on seasonal variations in monoterpene emissions potentials for two evergreen species (Quercus ilex and Pinus pinea) and used these data to construct two contrasting seasonal response functions for the inclusion in monoterpene emission models. We included these responses in the Niinemets et al. model and compared simulation results to those of the MEGAN model, both with and without its predicted seasonality. The effect of seasonality on regional monoterpene emissions inventories for European Mediterranean forests dominated by these species was tested for both models, using the GOTILWA+ biosphere model platform. The consideration of seasonality in the Niinemets et al. model reduced total estimated annual monoterpene emissions by up to 65% in some regions, with largest reductions at lower latitudes. The MEGAN model demonstrated a much weaker seasonal response than that in the Niinemets et al. model, and did not capture the between species seasonality differences found in this study. Results suggest that previous regional model inventories based on one fixed emission factor likely overestimate regional emissions, and species-specific expressions of seasonality may be necessary. The consideration of seasonality both largely reduces monoterpene emissions estimates, and changes their expected seasonal distribution.
Keywords: Holm oak; Italian stone pine; Models; regional inventory; Seasonality; VOC emissions

Seed weevils living on the edge: pressures and conflicts over body size in the endoparasitic Curculio larvae - Bonal, Raul; Muñoz, Alberto (Ecological Entomology, 2009)
Abstract 1. Body size in parasitic insects can be subjected to contrasting selective pressures, especially if they complete their development within a single host. On the one hand, a larger body size is associated with a higher fitness. On the other hand, the host offers a discrete amount of resources, thus constraining the evolution of a disproportionate body size. 2. The present study used the weevil Curculio elephas as a study model. Larvae develop within a single acorn, feeding on its cotyledons, and larval body size is strongly related to individual fitness. 3. The relationship between larval and acorn size was negatively exponential. Larval growth was constrained in small acorns, which did not provide enough food for the weevils to attain their potential size. Larval size increased and levelled off in acorns over a certain size (inflexion point), in which cotyledons were rarely depleted. When there were more than one larva per acorn, a larger acorn was necessary to avoid food depletion. 4. The results show that C. elephas larvae are sometimes endoparasitic, living on the edge of host holding capacity. If they were smaller they could avoid food depletion more easily, but the fitness benefits linked to a larger size have probably promoted body size increase. The strong negative effects of conspecific competition may have possibly influenced female strategy of laying a single egg per seed. 5. Being larger and fitter, but always within the limits of the available host sizes, may be one main evolutionary dilemma in endoparasites.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: acorn; Body size; Curculio; endoparasitism; food constraints; granivorous insects; Holm oak; host size; larvae

Seed weevils living on the edge: pressures and conflicts over body size in the endoparasitic Curculio larvae - Bonal, Raul; Muñoz, Alberto (Ecological Entomology, 2009)
Abstract 1. Body size in parasitic insects can be subjected to contrasting selective pressures, especially if they complete their development within a single host. On the one hand, a larger body size is associated with a higher fitness. On the other hand, the host offers a discrete amount of resources, thus constraining the evolution of a disproportionate body size. 2. The present study used the weevil Curculio elephas as a study model. Larvae develop within a single acorn, feeding on its cotyledons, and larval body size is strongly related to individual fitness. 3. The relationship between larval and acorn size was negatively exponential. Larval growth was constrained in small acorns, which did not provide enough food for the weevils to attain their potential size. Larval size increased and levelled off in acorns over a certain size (inflexion point), in which cotyledons were rarely depleted. When there were more than one larva per acorn, a larger acorn was necessary to avoid food depletion. 4. The results show that C. elephas larvae are sometimes endoparasitic, living on the edge of host holding capacity. If they were smaller they could avoid food depletion more easily, but the fitness benefits linked to a larger size have probably promoted body size increase. The strong negative effects of conspecific competition may have possibly influenced female strategy of laying a single egg per seed. 5. Being larger and fitter, but always within the limits of the available host sizes, may be one main evolutionary dilemma in endoparasites.
Keywords: acorn; Body size; Curculio; endoparasitism; food constraints; granivorous insects; Holm oak; host size; larvae

Acorn production in Spanish holm oak woodlands - Gea-Izquierdo, G.; Cañellas, I.; Montero, G. (Forest Systems, 2008)
We present a review on the state-of-the-art of fruit prodution in Western Iberia woodlands («dehesas»), and particularly in Q. ilex (holm oak) «dehesas». This threatened ecosystem is of very high ecological and economical importance. Quercus sp. fruits (acorns) are essential for wildlife, and for pig fattening in «dehesas». In the first part of this review we briefly describe the phenology of the holm oak and the factors affecting acorn morphology and chemical composition. In the second half we analyze the main known factors reported in the literature that determine acorn production: pruning, stand characteristics, and site (weather and soil). We make several suggestions to improve future research and detect the existing gaps in the undertanding of acorn production. Fruit production is highly variable, both between and within years and individuals. The mean production in «dehesas» (mean density circa 50 trees/ha) is around 250-600 kg/ha (≈100 g/canopy-m2 , CV> 100%). Acorn morphology is also very variable, with mean sound acorn size around 3.5 × 1.6 cm, CV ≈ 10% (3.5 g/acorn, CV > 50%). Silviculture plays an essential role in acorn production. Acorn production per tree seems to be negatively related to density. The effect of pruning is less clear: production seems to be reduced in the first and second years after pruning. After the third year it is not possible to discern from the literature whether there is any response to pruning or not. Weather and soil (site) also impact production and their effects should be explored in future management. The influence of genetics is unknown and should also be addressed. Longer data series are necessary. The dasometric features of the stands need to be characterized, in order to better understand production and compare results from different locations. Much research is still required to understand the functioning of fruiting in these woodlands.
Keywords: acorn; agrosilvopastoral systems; Dehesa; fruit production; Holm oak; Quercus ilex

Acorn production in Spanish holm oak woodlands - Gea-Izquierdo, G; Cañellas, I; Montero, G (Forest Systems, 2008)
We present a review on the state-of-the-art of fruit prodution in Western Iberia woodlands («dehesas»), and particularly in Q. ilex (holm oak) «dehesas». This threatened ecosystem is of very high ecological and economical importance. Quercus sp. fruits (acorns) are essential for wildlife, and for pig fattening in «dehesas». In the first part of this review we briefly describe the phenology of the holm oak and the factors affecting acorn morphology and chemical composition. In the second half we analyze the main known factors reported in the literature that determine acorn production: pruning, stand characteristics, and site (weather and soil). We make several suggestions to improve future research and detect the existing gaps in the undertanding of acorn production. Fruit production is highly variable, both between and within years and individuals. The mean production in «dehesas» (mean density circa 50 trees/ha) is around 250-600 kg/ha (≈100 g/canopy-m2 , CV> 100%). Acorn morphology is also very variable, with mean sound acorn size around 3.5 × 1.6 cm, CV ≈ 10% (3.5 g/acorn, CV > 50%). Silviculture plays an essential role in acorn production. Acorn production per tree seems to be negatively related to density. The effect of pruning is less clear: production seems to be reduced in the first and second years after pruning. After the third year it is not possible to discern from the literature whether there is any response to pruning or not. Weather and soil (site) also impact production and their effects should be explored in future management. The influence of genetics is unknown and should also be addressed. Longer data series are necessary. The dasometric features of the stands need to be characterized, in order to better understand production and compare results from different locations. Much research is still required to understand the functioning of fruiting in these woodlands.
Keywords: acorn; agrosilvopastoral systems; Dehesa; fruit production; Holm oak; Quercus ilex

Influence of pruning and the climatic conditions on acorn production in holm oak (Quercus ilex L.) dehesas in SW Spain - Alejano, R; TAPIAS, R; Fernández, M; Torres, Enrique; Alaejos, Joaquín; Domingo, Juan (Annals of Forest Science, 2008)
Acorn production by Quercus ilex L. ssp. ballota (Desf.) Samp. in SW Spain was assessed, and variations between years and the inﬂuence of pruning on it were examined. To this end, an experimental study was conducted at two diﬀerent sites (Calañas and San Bartolomé, in the province of Huelva) where trees were subjected to traditional (light, moderate or heavy) pruning and also to a new (crown-regeneration) pruning method. Acorn yield was quantiﬁed over a period of 5 years in the Calañas plot and 4 in the San Bartolomé plot, and found to average at 95.61 ± 0.76 g DM/m2 , which is equivalent to 6.5 ± 0.05 kg DM/tree; however, yield ﬁgures varied markedly between years depending on the particular climatic conditions. The average acorn production was correlated with the water potential in mid summer (end of July); the annual, spring and autumn rainfall; and the actual evapotranspiration for the period from September (previous year) to August. No signiﬁcant diﬀerences in acorn production between traditional pruning intensities were detected; in fact, there were only hints that heavy pruning might result in decreased acorn yields. The new pruning method used, crown-regeneration, seems promising with a view to increasing acorn yield; however, it should be tested on larger sample sizes before any ﬁnal conclusions can be drawn in this respect. Based on the results, the present health status of holm oaks in southwestern Spain (a result of sustained decline) and the low value of ﬁrewood – which used to be a very important source of income from pruning a few decades ago –, the authors recommend reducing the frequency and intensity of pruning in the dehesas of the study area.
Keywords: acorn production; Holm oak; Masting; pruning

Influence of pruning and the climatic conditions on acorn production in holm oak (Quercus ilex L.) dehesas in SW Spain - Alejano, R.; Tapias, R.; Fernández, M.; Torres, Enrique; Alaejos, Joaquín; Domingo, Juan (Annals of Forest Science, 2008)
Acorn production by Quercus ilex L. ssp. ballota (Desf.) Samp. in SW Spain was assessed, and variations between years and the inﬂuence of pruning on it were examined. To this end, an experimental study was conducted at two diﬀerent sites (Calañas and San Bartolomé, in the province of Huelva) where trees were subjected to traditional (light, moderate or heavy) pruning and also to a new (crown-regeneration) pruning method. Acorn yield was quantiﬁed over a period of 5 years in the Calañas plot and 4 in the San Bartolomé plot, and found to average at 95.61 ± 0.76 g DM/m2 , which is equivalent to 6.5 ± 0.05 kg DM/tree; however, yield ﬁgures varied markedly between years depending on the particular climatic conditions. The average acorn production was correlated with the water potential in mid summer (end of July); the annual, spring and autumn rainfall; and the actual evapotranspiration for the period from September (previous year) to August. No signiﬁcant diﬀerences in acorn production between traditional pruning intensities were detected; in fact, there were only hints that heavy pruning might result in decreased acorn yields. The new pruning method used, crown-regeneration, seems promising with a view to increasing acorn yield; however, it should be tested on larger sample sizes before any ﬁnal conclusions can be drawn in this respect. Based on the results, the present health status of holm oaks in southwestern Spain (a result of sustained decline) and the low value of ﬁrewood – which used to be a very important source of income from pruning a few decades ago –, the authors recommend reducing the frequency and intensity of pruning in the dehesas of the study area.
Keywords: acorn production; Holm oak; Masting; pruning

Leaf flavonoid content in Quercus ilex L. resprouts and its seasonal variation - Brossa, R.; Casals, I.; Pintó-Marijuan, M.; Fleck, I. (Trees, 2008)
Here, we provide the ﬁrst report on ﬂavonoid content in holm oak (Quercus ilex L.) leaves, analyzed by HPLC–MS/MS. Flavanols and ﬂavonols were the predominant groups, although proanthocyanidins and many soluble tannins had a relevant presence in all leaf samples. Seasonal variation of ﬂavonoids was determined in extracts from Q. ilex leaves during resprouting after a forest ﬁre in two Mediterranean forests. Similar seasonal trends were observed over 2 years during the two main stress seasons (winter and summer). The most abundant ﬂavonoid was the ﬂavanol epicatechin, which showed similar values during the two seasons. Hexosides of the ﬂavonols, quercetin, kaempferol and rhamnetin showed considerably higher content in winter, especially at the lowest temperatures. These variations in both forests are discussed on the basis of the chlorophyll ﬂuorescence results obtained. Anthocyanins were found practically absent in mature leaves. Nutrient or water availability differences between sites or seasons were not related to changes in leaf ﬂavonolhexoside content.
Keywords: á; á hplc; chlorophyll fluorescence; chlorophyll fluorescence á flavanols; esi; flavanols; flavonol-hexosides; flavonol-hexosides á holm oak; Holm oak; HPLC–ESI–MS/MS; ms

Leaf flavonoid content in Quercus ilex L. resprouts and its seasonal variation - Brossa, R.; Casals, I.; Pintó-Marijuan, M.; Fleck, I. (Trees, 2008)
Here, we provide the ﬁrst report on ﬂavonoid content in holm oak (Quercus ilex L.) leaves, analyzed by HPLC–MS/MS. Flavanols and ﬂavonols were the predominant groups, although proanthocyanidins and many soluble tannins had a relevant presence in all leaf samples. Seasonal variation of ﬂavonoids was determined in extracts from Q. ilex leaves during resprouting after a forest ﬁre in two Mediterranean forests. Similar seasonal trends were observed over 2 years during the two main stress seasons (winter and summer). The most abundant ﬂavonoid was the ﬂavanol epicatechin, which showed similar values during the two seasons. Hexosides of the ﬂavonols, quercetin, kaempferol and rhamnetin showed considerably higher content in winter, especially at the lowest temperatures. These variations in both forests are discussed on the basis of the chlorophyll ﬂuorescence results obtained. Anthocyanins were found practically absent in mature leaves. Nutrient or water availability differences between sites or seasons were not related to changes in leaf ﬂavonolhexoside content.
Keywords: á; á hplc; chlorophyll fluorescence; chlorophyll fluorescence á flavanols; esi; flavanols; flavonol-hexosides; flavonol-hexosides á holm oak; Holm oak; HPLC–ESI–MS/MS; ms

Opzioni selvicolturali su cedui di leccio del Gargano: risultati a 14 anni dall'avvio della sperimentazione - La Marca, O; Marziliano, P A; Scopigno, D (iForest - Biogeosciences and Forestry, 2008)
In the frame of a long-term research program concerning management of ageing holm oak coppices, results available after 14 growing seasons are reported in present paper. Experimental treatments include: A) 50 standards per hectare, all of the same age; B) 250 standards per hectare, all of the same age; C) 140 standards per hectare, with two different ages; D) conversion to high forest; E) natural evolution (control). A total of 15 permanent plots were established (5 treatments x 3 replicates per treatment) and the experimental design used is that of randomised blocks. Based on observations concerning seedlings and shoots development and standards growth and competitive effects, the following preliminary results may be highlighted: i) recovering the traditional coppicing system with few standards per hectare represents a valid option from both ecological and shoots growth point of view; the stools, with few standards per hectare, showed a larger number of sprouts, provided with a higher average height and larger diameters; ii) uneven-aged standards represent a good alternative form the points of view of both landscape impact immediately after felling operations and stand resistance to climatic damages; iii) a good alternative is to apply conversion treatments to high forest, whenever their site quality allows these operations.
Keywords: Conversion To High Forest; coppice; Holm oak; Regeneration; Standard Density

Environmental heterogeneity, bird-mediated directed dispersal, and oak woodland dynamics in Mediterranean Spain - Purves, Drew W.; Zavala, Miguel A.; Ogle, Kiona; Prieto, Fernando; Benayas, Jose M. Rey (ECOLOGICAL MONOGRAPHS, 2007)
Vegetation dynamics in complex landscapes depend on interactions among environmental heterogeneity, disturbance, habitat fragmentation, and seed dispersal processes. We explore how these features combine to affect the regional abundances and distributions of three Quercus (oak) species in central Spain: Q. faginea (deciduous tree), Q. ilex (evergreen tree), and Q. coccifera (evergreen shrub). We develop and parameterize a stochastic patch occupancy model (SPOM) that, unlike previous SPOMs, includes environmentally driven variation in disturbance and establishment. Dispersal in the model is directed toward local (nearby) suitable habitat patches, following the observed seed-caching behavior of the European Jay. Model parameters were estimated using Bayesian methods and survey data from 12 047 plots. Model simulations were conducted to explore the importance of different dispersal modes (local directed, global directed, local random, global random). The SPOM with local directed dispersal gave a much better fit to the data and reproduced observed regional abundance, abundance-environment correlations, and spatial autocorrelation in abundance for all three species. Model simulations suggest that jay-mediated directed dispersal increases regional abundance and alters species-environment correlations. Local dispersal is estimated to reduce regional abundances, amplify species-environment correlations, and amplify spatial autocorrelation. Parameter estimates and model simulations reveal important species-specific differences in sensitivity to environmental perturbations and dispersal mode. The dominant species Q. ilex is estimated to be highly fecund, but on the edge of its climatic tolerance. Therefore Q. ilex gains little from directed dispersal, suffers little from local dispersal, and is relatively insensitive to changes in habitat cover or disturbance rate; but Q. ilex is highly sensitive to altered drought length. In contrast, the rarest species, Q. coccifera, is well adapted to the climate and soils but has low fecundity; thus, it is highly sensitive to changes in dispersal, habitat cover, and disturbance but insensitive to altered drought length. Finally, Q. faginea is estimated to be both at the edge of its climatic tolerance and to have low fecundity, making it sensitive to all perturbations. Apparently, co-occurring species can exhibit very different interactions among dispersal, environmental characteristics, and physiological tolerances, calling for increased attention to species-specific dynamics in determining regional vegetation responses to anthropogenic perturbations.
The following values have no corresponding Zotero field: pub-location: 1707 H ST NW, STE 400, WASHINGTON, DC 20006-3915 USA publisher: ECOLOGICAL SOC AMER
Keywords: biogeography; climate change; climate envelope; corvids; dispersal limitation; Garrulus; Holm oak; Iberian peninsular; incidence function; patch model; species migration; zoochory

Environmental heterogeneity, bird-mediated directed dispersal, and oak woodland dynamics in Mediterranean Spain - Purves, Drew W; Zavala, MIGUEL a; Ogle, Kiona; Prieto, Fernando; Benayas, Jose M Rey (ECOLOGICAL MONOGRAPHS, 2007)
Vegetation dynamics in complex landscapes depend on interactions among environmental heterogeneity, disturbance, habitat fragmentation, and seed dispersal processes. We explore how these features combine to affect the regional abundances and distributions of three Quercus (oak) species in central Spain: Q. faginea (deciduous tree), Q. ilex (evergreen tree), and Q. coccifera (evergreen shrub). We develop and parameterize a stochastic patch occupancy model (SPOM) that, unlike previous SPOMs, includes environmentally driven variation in disturbance and establishment. Dispersal in the model is directed toward local (nearby) suitable habitat patches, following the observed seed-caching behavior of the European Jay. Model parameters were estimated using Bayesian methods and survey data from 12 047 plots. Model simulations were conducted to explore the importance of different dispersal modes (local directed, global directed, local random, global random). The SPOM with local directed dispersal gave a much better fit to the data and reproduced observed regional abundance, abundance-environment correlations, and spatial autocorrelation in abundance for all three species. Model simulations suggest that jay-mediated directed dispersal increases regional abundance and alters species-environment correlations. Local dispersal is estimated to reduce regional abundances, amplify species-environment correlations, and amplify spatial autocorrelation. Parameter estimates and model simulations reveal important species-specific differences in sensitivity to environmental perturbations and dispersal mode. The dominant species Q. ilex is estimated to be highly fecund, but on the edge of its climatic tolerance. Therefore Q. ilex gains little from directed dispersal, suffers little from local dispersal, and is relatively insensitive to changes in habitat cover or disturbance rate; but Q. ilex is highly sensitive to altered drought length. In contrast, the rarest species, Q. coccifera, is well adapted to the climate and soils but has low fecundity; thus, it is highly sensitive to changes in dispersal, habitat cover, and disturbance but insensitive to altered drought length. Finally, Q. faginea is estimated to be both at the edge of its climatic tolerance and to have low fecundity, making it sensitive to all perturbations. Apparently, co-occurring species can exhibit very different interactions among dispersal, environmental characteristics, and physiological tolerances, calling for increased attention to species-specific dynamics in determining regional vegetation responses to anthropogenic perturbations.
Keywords: biogeography; climate change; climate envelope; corvids; dispersal limitation; Garrulus; Holm oak; Iberian peninsular; incidence function; patch model; species migration; zoochory

Influence of different post-planting treatments on the development in Holm oak afforestation - Jiménez, M. N.; Fernández-Ondoño, E.; Ripoll, M. A.; Navarro, F. B.; Gallego, E.; De Simón, E.; Lallena, a. M.; Simón, E; Lallena, a. M. (Trees, 2007)
This work examines the inﬂuence of different post-planting treatments in the development of afforested Holm oak, Quercus ilex L. subsp. ballota (Desf.) Samp., in an abandoned agricultural ﬁeld in SE Spain. A total of nine post-planting treatments were carried out: tilling spring and autumn in different years, spreading of organic and inorganic mulch, irrigation in different periods. Soil preparation prior to planting consisted of digging of a hole with a backhoe excavator of 80 HP and homogenized the proﬁle characteristics. Survival, nutrient concentrations in both leaves and soil, and foliage surface have been studied. Dryseason irrigation every 2 weeks provided the best survival rate (98.3%), while mulching with solid urban wastes caused the worst results (6.6%). The supply of forest debris increased the N, K, and Mn concentrations at all depths with respect to the other treatments, and the solid urban waste had the same effect in N, P, K, Na, Cu, Fe, and Zn. All the foliar nutrients decreased in 2005 with respect to the 2004 sampling, except in N, Cu, and Zn. The use of foliar nutrient concentrations, together with the increase in leaf surface is proposed as a non-destructive index of development and of forestation stands in the ﬁrst stages of growth. The application of forest debris, and particularly the placement of boulders in the beds of individual trees proved most effective in sapling development.
Keywords: á; á semi-arid; Afforestation; afforestation á post-planting treatments; Holm oak; holm oak á nutrients; Nutrients; Post-planting treatments; semi-arid

CERAMBICIDOS XILOFAGOS DEENCINAS Y ALCORNOQUES: ESTUDIO BIOECOLOGICO Y CONTROL DEPOBLACIONES - López Pantoja, G; Sánchez-Osorio, I; Domínguez, L (Bol. Inf. CIDEU, 2006)
The aim of this work is to present recent advances on the knowledge of holm oak and cork oak woodborers (Coleoptera: Cerambycidae) in Huelva (Andalussia, Spain). Cerambyx welensii and Prinobius germari are considered the main implicated species. We emphasize over the differences of behavior founded among them: the first species is little territorial and very movable, Prinobius seems to show a more territorial and sedentary behavior, specially the males. After the analysis of diverse options for population control of insects with similar habits, a strategy of Integrated Management is recommended, having as one of his pillars the attraction of these species for his capture and/or the specific repelence or confusion; that is to say, the applied study of semiochemicals compounds to integrated pest management.
Keywords: Cerambyx; Cork oak; ehavior; Holm oak; Integrated Pest Management; Prinobius; woodborers

CERAMBICIDOS XILOFAGOS DEENCINAS Y ALCORNOQUES: ESTUDIO BIOECOLOGICO Y CONTROL DEPOBLACIONES - López Pantoja, G.; Sánchez-Osorio, I.; Domínguez, L. (Bol. Inf. CIDEU, 2006)
The aim of this work is to present recent advances on the knowledge of holm oak and cork oak woodborers (Coleoptera: Cerambycidae) in Huelva (Andalussia, Spain). Cerambyx welensii and Prinobius germari are considered the main implicated species. We emphasize over the differences of behavior founded among them: the first species is little territorial and very movable, Prinobius seems to show a more territorial and sedentary behavior, specially the males. After the analysis of diverse options for population control of insects with similar habits, a strategy of Integrated Management is recommended, having as one of his pillars the attraction of these species for his capture and/or the specific repelence or confusion; that is to say, the applied study of semiochemicals compounds to integrated pest management.
Keywords: Cerambyx; Cork oak; ehavior; Holm oak; Integrated Pest Management; Prinobius; woodborers

Fire effects on the composition of Pinus halepensis and Quercus rotundifolia communities in the Bou-Taleb Forest, Algeria, with application of a multivariable analysis - Madoui, Amar; Goldammer, Johann G (Forest Ecology and Management, 2006)
The effect of forest ﬁre on the ﬂora of Bou-Taleb’s forest was studied using a Factorial Correspondence Analysis (FCA). This analysis, implemented by using the Braun-Blanquet method, was applied on ﬂoristic releves investigated on Aleppo pine (Pinus halepensis) and on Holm oak (Quercus rotundifolia) communities which burned at different dates. Other ones represent the non-burnt communities and were used as control. Two analyses were used with all releves (160) and all the species which f > 1 (323). The ﬁrst analysis is applied with a presence-absence coefﬁcient and the second one with an abundance-dominance coefﬁcient. The third analysis involved only releves of burned communities (98) and all species (361). The results of all analyses show the time elapsed since ﬁre (ﬂoristic age) is a discrimination factor. We found a clear separation of young communities on the one side, which appeared immediately after ﬁre, and older communities on the other side. Also, ﬁre effects were linked to the type of communities. There is a distinct difference between Aleppo pine and Holm oak communities. There is invasion of therophytes on the parcels recently burned. Few years after ﬁre, the ﬂoristic composition and structure of communities will be the same as on unburned sites.
Keywords: Aleppo pine; Algeria; FCA; Forest ﬁres; Holm oak; Pinus halepensis; Quercus rotundifolia

Fire effects on the composition of Pinus halepensis and Quercus rotundifolia communities in the Bou-Taleb Forest, Algeria, with application of a multivariable analysis - Madoui, Amar; Goldammer, Johann G. (Forest Ecology and Management, 2006)
The effect of forest ﬁre on the ﬂora of Bou-Taleb’s forest was studied using a Factorial Correspondence Analysis (FCA). This analysis, implemented by using the Braun-Blanquet method, was applied on ﬂoristic releves investigated on Aleppo pine (Pinus halepensis) and on Holm oak (Quercus rotundifolia) communities which burned at different dates. Other ones represent the non-burnt communities and were used as control. Two analyses were used with all releves (160) and all the species which f > 1 (323). The ﬁrst analysis is applied with a presence-absence coefﬁcient and the second one with an abundance-dominance coefﬁcient. The third analysis involved only releves of burned communities (98) and all species (361). The results of all analyses show the time elapsed since ﬁre (ﬂoristic age) is a discrimination factor. We found a clear separation of young communities on the one side, which appeared immediately after ﬁre, and older communities on the other side. Also, ﬁre effects were linked to the type of communities. There is a distinct difference between Aleppo pine and Holm oak communities. There is invasion of therophytes on the parcels recently burned. Few years after ﬁre, the ﬂoristic composition and structure of communities will be the same as on unburned sites.
Keywords: Aleppo pine; Algeria; FCA; Forest ﬁres; Holm oak; Pinus halepensis; Quercus rotundifolia

The Holm Oak leaf proteome: Analytical and biological variability in the protein expression level assessed by 2-DE and protein identification tandem mass spectrometry de novo sequencing and sequence similarity searching - Jorge, Inmaculada; Navarro, Rafael M; Lenz, Christof; Ariza, David; Porras, Carlos; Jorrín, Jesús (PROTEOMICS, 2005)
As a first approach in establishing the holm oak leaf proteome, we have optimised a protocol for this plant and tissue which includes the following steps: trichloroacetic acid-acetone extraction, two-dimensional gel electrophoresis (2-DE) on pH 5 to 8 linear gradient immobilised pH gradient strips as the first dimension, and sodium dodecyl sulfate-polyacrylamide gel electrophoresis on 13% polyacrylamide gels as the second one. Proteins were detected by Coomassie staining. Gel images were recorded and digitalized, and the protein spots quantified by using a linear regression equation of protein quantity on spot volume obtained against standard proteins. Analytical variance was calculated for one-hundred protein spots from three replicate 2-DE gels of the same protein extract. Biological variance was determined for the same protein spots from independent tissue extracts corresponding to leaves from different trees, or the same tree at different orientations or sampling times during a day. Values of 26% for the analytical variance and 58.6% for the biological variance among independent trees were obtained. These values provide a quantified and statistical basis for the evaluation of protein expression changes in comparative proteomic investigations with this species. A representative set of the major proteins, covering the isoelectric point range of 5 to 8 and the relative molecular massr range of 14 to 78 kDa, were subjected to liquid chromatography-tandem mass spectrometry analysis. Due to the absence of Quercus DNA or protein sequence databases, a method based on the procedure reported by Liska and Shevchenko [1] including de novo sequencing and BLAST similarity searching against other plant species databases was used for protein identification. Out of 43 analysed spots, 35 were positively identified. The identified proteins mainly corresponded to enzymes involved in photosynthesis and energetic metabolism, with a significant number corresponding to RubisCO.
Keywords: De novo sequencing; Holm oak; Leaf proteome; Tandem mass spectrometry; Two-dimensional gel electrophoresis

Ozone uptake by an evergreen Mediterranean Forest () in Italy. Part I: Micrometeorological flux measurements and flux partitioning - Gerosa, G; Vitale, M; Finco, A; Manes, F; Denti, A; Cieslik, S (Atmospheric Environment, 2005)
Ozone, water and energy ﬂuxes have been measured over a Mediterranean evergreen forest in Central Italy from August to October 2003 with the eddy-correlation technique in order to evaluate the amount of ozone taken up by plants in dry summer and in mild autumn conditions. The stomatal ozone ﬂuxes have been calculated using the analogy with water vapor ﬂuxes inside the stomata, which are easily measurable. The total ozone dose was obtained by integrating the stomatal ﬂuxes over time. Stomatal ﬂux resulted a minor part (31.5%) of the total ozone ﬂux over the forest ecosystem. The main part of ozone deposition follows non-stomatal pathways. Chemical sink seems to play a relevant role in the morning non-stomatal deposition. Stomatal uptake is enhanced by water availability but, on the average, it does not exceed the 34.4% of the total ozone ﬂux. A comparison between the cumulated stomatal ozone ﬂuxes and the currently used AOT40 exposure index highlighted important distortions introduced by this index. AOT40, which do not take into account plant physiology, lead to substantial overestimation of ozone risk, particularly when water supply is limited, as occurs frequently in Southern European and Mediterranean areas.
Keywords: Holm oak; mediterranean forest ecosystem; ozone deposition; Stomatal uptake

Ozone uptake by an evergreen Mediterranean Forest () in Italy. Part I: Micrometeorological flux measurements and flux partitioning - Gerosa, G.; Vitale, M.; Finco, A.; Manes, F.; Denti, A.; Cieslik, S. (Atmospheric Environment, 2005)
Ozone, water and energy ﬂuxes have been measured over a Mediterranean evergreen forest in Central Italy from August to October 2003 with the eddy-correlation technique in order to evaluate the amount of ozone taken up by plants in dry summer and in mild autumn conditions. The stomatal ozone ﬂuxes have been calculated using the analogy with water vapor ﬂuxes inside the stomata, which are easily measurable. The total ozone dose was obtained by integrating the stomatal ﬂuxes over time. Stomatal ﬂux resulted a minor part (31.5%) of the total ozone ﬂux over the forest ecosystem. The main part of ozone deposition follows non-stomatal pathways. Chemical sink seems to play a relevant role in the morning non-stomatal deposition. Stomatal uptake is enhanced by water availability but, on the average, it does not exceed the 34.4% of the total ozone ﬂux. A comparison between the cumulated stomatal ozone ﬂuxes and the currently used AOT40 exposure index highlighted important distortions introduced by this index. AOT40, which do not take into account plant physiology, lead to substantial overestimation of ozone risk, particularly when water supply is limited, as occurs frequently in Southern European and Mediterranean areas.
Keywords: Holm oak; mediterranean forest ecosystem; ozone deposition; Stomatal uptake

Pathogenicity of three Phytophthora spp. causing late seedling rot of Quercus ilex ssp. ballota - Sanchez, M. E.; Andicoberry, S.; Trapero, A. (Forest Pathology, 2005)
Within a research project on quality of plants for forestation of agricultural lands, we studied the aetiology of a late seedling rot affecting holm oak (Quercus ilex ssp. ballota) in two forest nurseries in southern Spain. Major disease symptoms were foliage wilting and necrosis of feeder roots. Phytophthora cinnamomi, Phytophthora cryptogea and Phytophthora drechsleri were isolated from necrotic roots of holm oaks. Selected isolates of the three Phytophthora species were pathogenic to Quercus ilex ssp. ballota and Quercus suber seedlings in artificial inoculations. Soil flooding conditions were essential for infection and root rot development. There was no host specificity among the species, the isolates of P. cinnamomi being the most virulent in all inoculated plants. In these inoculations, Q. ilex ssp. ballota plants were more susceptible than those of Q. suber. This work is the first report of P. cinnamomi, P. drechsleri and P. cryptogea affecting Q. ilex ssp. ballota in forest nurseries.
The following values have no corresponding Zotero field: publisher: Blackwell Verlag GmbH
Keywords: Holm oak; Nurseries (voyant); Phytophthora spp.; root rot; Soil water content

Pathogenicity of three Phytophthora spp. causing late seedling rot of Quercus ilex ssp. ballota - SÁNCHEZ, M E; Andicoberry, S; TRAPERO, A (Forest Pathology, 2005)
Within a research project on quality of plants for forestation of agricultural lands, we studied the aetiology of a late seedling rot affecting holm oak (Quercus ilex ssp. ballota) in two forest nurseries in southern Spain. Major disease symptoms were foliage wilting and necrosis of feeder roots. Phytophthora cinnamomi, Phytophthora cryptogea and Phytophthora drechsleri were isolated from necrotic roots of holm oaks. Selected isolates of the three Phytophthora species were pathogenic to Quercus ilex ssp. ballota and Quercus suber seedlings in artificial inoculations. Soil flooding conditions were essential for infection and root rot development. There was no host specificity among the species, the isolates of P. cinnamomi being the most virulent in all inoculated plants. In these inoculations, Q. ilex ssp. ballota plants were more susceptible than those of Q. suber. This work is the first report of P. cinnamomi, P. drechsleri and P. cryptogea affecting Q. ilex ssp. ballota in forest nurseries.
Keywords: Holm oak; Nurseries (voyant); Phytophthora spp.; root rot; Soil water content

Sustained accumulation of methyl salicylate alters antioxidant protection and reduces tolerance of holm oak to heat stress - Llusia, Joan; Penuelas, Josep; Munné-Bosch, Sergi (Physiologia Plantarum, 2005)
Methyl salicylate (MeSA) is thought to have a major role in biotic and abiotic stresses by acting as a signal to trigger the oxidative burst, which is needed to activate gene expression in plant stress responses. To assess the potential effects of sustained foliar accumulation of MeSA on plant stress tolerance, the extent of photo- and antioxidant protection, lipid peroxidation and visual leaf area damage were evaluated in MeSA-treated (c. 60 nl l−1 in air) and control holm oak (Quercus ilex L.) plants exposed to heat stress. Control plants showed an increase in foliar MeSA levels up to 1.8 nmol [gDW]−1 as temperature increased and they displayed tolerance to temperatures as high as 45°C, which might be attributed, at least in part, to enhanced xanthophyll de-epoxidation and increases in ascorbate and α-tocopherol. MeSA-treated plants showed a sustained foliar accumulation of this compound, with values ranging from 10 to 23 nmol [gDW]−1 throughout the experiment. These plants showed lower ascorbate and tocopherol levels and higher oxidative damage at 50°C than controls, as indicated by enhanced malondialdehyde levels and leaf area damage and lower maximum efficiency of PSII photochemistry (Fv/Fm ratio). These results demonstrate that a sustained foliar accumulation of MeSA is detrimental to plant function and that it can reduce thermotolerance in holm oak by altering antioxidant defences.
The following values have no corresponding Zotero field: publisher: Munksgaard International Publishers
Keywords: antioxidant protection (voyant); foliar MeSA accumulation; heat stress; Holm oak; methyl salicylate

Climatic factors and establishment of Quercus ilex-communities in Trieste Province (NE Italy) - Codogno, M.; Furlanetto, A. (Annali di Botanica, 2004)
In the coastal area called "Cernizza" (near Duino. ca 15 km NW from Trieste), at an altitude between 0 and 40 m. is located a wood vegetation complex characterized by Quercus ilex and Carpinus orientalis. The bedrocks of this site is carbonatic. This wood vegetation does not occur in other sites or the Trieste province, where deciduous oak woods (Q. pubescells, Q. petraea s.1.) are dominant both on arenaceus and on carbonatic rocks. Other Quercus ilex communities are occurring only as scrubs on the calcareous coastal cliffs characterized by primitive lithosoils. In order to detect if this wood community might be an expression of the c1imate dominating this particular zone, some Duino's c1imatic data, relative lo a record period of 9 years. have been compared with the Trieste's ones. The analysed parameters were the following: air temperature. rainfall, evaporation. wind speed and relative humidity. From the comparison of these paramenters it emerged that the Duino's climate is more humid than the Trieste's one. Only in springtime Duino is less rainy than Trieste according lo the analysis of the monthly mean values of precipitation. From the ecophysiological point of view, a study of the seasonal changes of the root hydraulic conductance in some forest trees (Nardini el al .. 1998) has pointed out the superiority of Quercus ilex compared to Quercus pubescens, as regards the competitive ability of the seedlings during the spring. For this reason, the smaller spring rainfall could explain the occurrence of Quercus ilex stands not only in the neighbourhood of Duino but also at the beginning of the large valleys characterized by S•N direction in the South Eastern Alps.
Keywords: climate; Holm oak; plant ecology; Quercus ilex; Trieste province; Vegetation

Climatic factors and establishment of Quercus ilex-communities in Trieste Province (NE Italy) - Codogno, M; Furlanetto, A (Annali di Botanica, 2004)
In the coastal area called "Cernizza" (near Duino. ca 15 km NW from Trieste), at an altitude between 0 and 40 m. is located a wood vegetation complex characterized by Quercus ilex and Carpinus orientalis. The bedrocks of this site is carbonatic. This wood vegetation does not occur in other sites or the Trieste province, where deciduous oak woods (Q. pubescells, Q. petraea s.1.) are dominant both on arenaceus and on carbonatic rocks. Other Quercus ilex communities are occurring only as scrubs on the calcareous coastal cliffs characterized by primitive lithosoils. In order to detect if this wood community might be an expression of the c1imate dominating this particular zone, some Duino's c1imatic data, relative lo a record period of 9 years. have been compared with the Trieste's ones. The analysed parameters were the following: air temperature. rainfall, evaporation. wind speed and relative humidity. From the comparison of these paramenters it emerged that the Duino's climate is more humid than the Trieste's one. Only in springtime Duino is less rainy than Trieste according lo the analysis of the monthly mean values of precipitation. From the ecophysiological point of view, a study of the seasonal changes of the root hydraulic conductance in some forest trees (Nardini el al .. 1998) has pointed out the superiority of Quercus ilex compared to Quercus pubescens, as regards the competitive ability of the seedlings during the spring. For this reason, the smaller spring rainfall could explain the occurrence of Quercus ilex stands not only in the neighbourhood of Duino but also at the beginning of the large valleys characterized by S•N direction in the South Eastern Alps.
Keywords: climate; Holm oak; plant ecology; Quercus ilex; Trieste province; Vegetation

Diversity and fruiting patterns of ectomycorrhizal and saprobic fungi in an old-growth Mediterranean forest dominated by Quercus ilex L. - Richard, F; Moreau, P -A; Selosse, M -A; Gardes, M (Canadian Journal of Botany, 2004)
We collected and mapped epigeous fruitbodies of both ectomycorrhizal (ECM) and saprobic fungi in an oldgrowth Quercus ilex L. Mediterranean forest within a permanent transect of 6400 m2 over three consecutive fruiting seasons. Out of 5382 fruitbodies, a total of 234 species were found, including 166 and 68 ECM and saprobic taxa, respectively. Both communities were mainly composed of rare species. Two genera, Russula and Cortinarius, accounted for 34.4% of ECM fruitbodies and 50% of species diversity. The three most abundant ECM species were Laccaria laccata (Scop.: Fr.) Berk. & Broome, Inocybe tigrina R. Heim, and Lactarius chrysorrheus Fr. The fruiting ECM community encompassed a few Mediterranean species and numerous broad host range temperate species. We also analysed the fruiting patterns in relation to forest structure, host composition, and natural canopy gaps. The results showed (i) a significant correlation of species richness to tree density, (ii) a richness decrease as the number of vegetation layers increases, and (iii) a preferential fruiting of some species near Q. ilex or Arbutus unedo L. Another noteworthy feature was that richness and production were greatly enhanced in canopy gaps. Selective fruiting was also observed among species. These results highlight the importance of forest structure and large woody debris for fungal conservation.
doi: 10.1139/b04-128
Keywords: canopy gaps; ECM community; fungal conservation; Holm oak; macromycete fruiting patterns; saprophytic fungi

Diversity and fruiting patterns of ectomycorrhizal and saprobic fungi in an old-growth Mediterranean forest dominated by Quercus ilex L. - Richard, F.; Moreau, P.-A.; Selosse, M.-A.; Gardes, M. (Canadian Journal of Botany, 2004)
We collected and mapped epigeous fruitbodies of both ectomycorrhizal (ECM) and saprobic fungi in an oldgrowth Quercus ilex L. Mediterranean forest within a permanent transect of 6400 m2 over three consecutive fruiting seasons. Out of 5382 fruitbodies, a total of 234 species were found, including 166 and 68 ECM and saprobic taxa, respectively. Both communities were mainly composed of rare species. Two genera, Russula and Cortinarius, accounted for 34.4% of ECM fruitbodies and 50% of species diversity. The three most abundant ECM species were Laccaria laccata (Scop.: Fr.) Berk. & Broome, Inocybe tigrina R. Heim, and Lactarius chrysorrheus Fr. The fruiting ECM community encompassed a few Mediterranean species and numerous broad host range temperate species. We also analysed the fruiting patterns in relation to forest structure, host composition, and natural canopy gaps. The results showed (i) a significant correlation of species richness to tree density, (ii) a richness decrease as the number of vegetation layers increases, and (iii) a preferential fruiting of some species near Q. ilex or Arbutus unedo L. Another noteworthy feature was that richness and production were greatly enhanced in canopy gaps. Selective fruiting was also observed among species. These results highlight the importance of forest structure and large woody debris for fungal conservation.
doi: 10.1139/b04-128doi: 10.1139/b04-128The following values have no corresponding Zotero field: publisher: NRC Research Press
Keywords: canopy gaps; ECM community; fungal conservation; Holm oak; macromycete fruiting patterns; saprophytic fungi

The effect of low temperatures on the photosynthetic apparatus of Quercus ilex subsp. ballota at its lower and upper altitudinal limits in the Iberian peninsula and during a single freezing-thawing cycle - Corcuera, L.; Morales, F.; Abadia, A.; GIL-PELEGRÍN, E. (Trees, 2004)
We investigated the response of the photosynthetic apparatus during an episode of extreme low winter temperature in Quercus ilex subsp. ballota (Desf.) Samp., a typical Mediterranean evergreen species in the Iberian peninsula. Both plants in a woodland located at high altitude (1,177 m. a.s.l.) and potted plants obtained from acorns of the same populations grown at low altitude (225 m. a.s.l.) were analyzed. Net CO2 assimilation rate was negative and there was a marked decrease in photosystem II (PSII) efficiency during winter in leaves of the woodland population (high altitude individuals). These processes were accompanied by increases in nonphotochemical quenching (NPQ) and in the de-epoxidated carotenoids within the xanthophyll cycle, mechanisms aimed to dissipate excess energy. In addition, these deepoxidated carotenoids were largely preserved during the night. There was no chlorophyll bleaching during the winter, which suggests that leaves were not experiencing photoinhibitory damage. In fact, the net photosynthetic rate and the PSII efficiency recovered in spring. These changes were not observed, or were much more reduced, in individuals located at lower altitude after a few frosts. When the response to rapid temperature changes (from 20°C to −5°C and from −5°C to 20°C) was studied, it was found that the maximum potential PSII efficiency was fairly stable, ranging from 0.70 to 0.75. The rest of the photosynthetic parameters measured, actual and intrinsic PSII efficiency, photochemical and NPQ, responded immediately to the changes in temperature and, also, the recovery after cold events was practically immediate.
Keywords: chlorophyll fluorescence; Holm oak; photochemical and non-photochemical quenching; photoprotection; photosystem ii efficiency

The effect of low temperatures on the photosynthetic apparatus of Quercus ilex subsp. ballota at its lower and upper altitudinal limits in the Iberian peninsula and during a single freezing-thawing cycle - Corcuera, L; Morales, F; Abadía, A; Gil-Pelegrín, E (Trees, 2004)
We investigated the response of the photosynthetic apparatus during an episode of extreme low winter temperature in Quercus ilex subsp. ballota (Desf.) Samp., a typical Mediterranean evergreen species in the Iberian peninsula. Both plants in a woodland located at high altitude (1,177 m. a.s.l.) and potted plants obtained from acorns of the same populations grown at low altitude (225 m. a.s.l.) were analyzed. Net CO2 assimilation rate was negative and there was a marked decrease in photosystem II (PSII) efficiency during winter in leaves of the woodland population (high altitude individuals). These processes were accompanied by increases in nonphotochemical quenching (NPQ) and in the de-epoxidated carotenoids within the xanthophyll cycle, mechanisms aimed to dissipate excess energy. In addition, these deepoxidated carotenoids were largely preserved during the night. There was no chlorophyll bleaching during the winter, which suggests that leaves were not experiencing photoinhibitory damage. In fact, the net photosynthetic rate and the PSII efficiency recovered in spring. These changes were not observed, or were much more reduced, in individuals located at lower altitude after a few frosts. When the response to rapid temperature changes (from 20°C to −5°C and from −5°C to 20°C) was studied, it was found that the maximum potential PSII efficiency was fairly stable, ranging from 0.70 to 0.75. The rest of the photosynthetic parameters measured, actual and intrinsic PSII efficiency, photochemical and NPQ, responded immediately to the changes in temperature and, also, the recovery after cold events was practically immediate.
Keywords: chlorophyll fluorescence; Holm oak; photochemical and non-photochemical quenching; photoprotection; photosystem ii efficiency

Nursery cultivation regimes, plant functional attributes, and field performance relationships in the Mediterranean oak Quercus ilex L. - VILLAR-SALVADOR, P; Planelles, R; Enrı́quez, E; Rubira, J.Peñuelas (Forest Ecology and Management, 2004)
In this study we have addressed the effect of nitrogen fertilisation and shading used during nursery growth on the functional quality of Quercus ilex L. (holm oak) seedlings and their outplanting performance in an abandoned continental Mediterranean cropland. Three N fertilisation regimes: high and low fertilisation (154 and 34 mg N per plant, respectively) and no fertilisation, combined with two shade levels (full sun and 45% shade) were studied. Fertilisation increased the shoot size, shoot to root mass ratio (S/R), root N, and both shoot and root P concentration of the plants produced in the nursery. Fertilisation also enhanced the capacity of new root formation. Neither tissue K nor root mass was affected by N fertilisation. Shading increased S/R and root K concentration but reduced both shoot and root N concentration. Two years after planting, unfertilised seedlings had higher mortality and grew signiﬁcantly less than those cultivated at both a low and a high fertilisation level. Shading during nursery growth had no inﬂuence on the outplanting performance of holm oak seedlings. Plants with a larger shoot and higher S/R had lower mortality and grew faster than those with a smaller shoot and lower S/R. Outplanting performance of holm oak seedlings was related with root N and P concentration and with RGC. No relationship was found with either shoot nutrient concentration or root mass. We conclude that high N fertilisation of holm oak seedlings in the nursery can improve their early ﬁeld establishment in the afforestation Mediterranean abandoned croplands.
Keywords: Afforestation; Holm oak; nitrogen; nursery fertilisation; root growth capacity; shading

Nursery cultivation regimes, plant functional attributes, and field performance relationships in the Mediterranean oak Quercus ilex L. - Villar-Salvador, P.; Planelles, R.; Enrı́quez, E.; Rubira, J. Peñuelas (Forest Ecology and Management, 2004)
In this study we have addressed the effect of nitrogen fertilisation and shading used during nursery growth on the functional quality of Quercus ilex L. (holm oak) seedlings and their outplanting performance in an abandoned continental Mediterranean cropland. Three N fertilisation regimes: high and low fertilisation (154 and 34 mg N per plant, respectively) and no fertilisation, combined with two shade levels (full sun and 45% shade) were studied. Fertilisation increased the shoot size, shoot to root mass ratio (S/R), root N, and both shoot and root P concentration of the plants produced in the nursery. Fertilisation also enhanced the capacity of new root formation. Neither tissue K nor root mass was affected by N fertilisation. Shading increased S/R and root K concentration but reduced both shoot and root N concentration. Two years after planting, unfertilised seedlings had higher mortality and grew signiﬁcantly less than those cultivated at both a low and a high fertilisation level. Shading during nursery growth had no inﬂuence on the outplanting performance of holm oak seedlings. Plants with a larger shoot and higher S/R had lower mortality and grew faster than those with a smaller shoot and lower S/R. Outplanting performance of holm oak seedlings was related with root N and P concentration and with RGC. No relationship was found with either shoot nutrient concentration or root mass. We conclude that high N fertilisation of holm oak seedlings in the nursery can improve their early ﬁeld establishment in the afforestation Mediterranean abandoned croplands.
Keywords: Afforestation; Holm oak; nitrogen; nursery fertilisation; root growth capacity; shading

Spatial patterns in long-distance dispersal of Quercus ilex acorns by jays in a heterogeneous landscape - Gómez, José María (Ecography, 2003)
In this paper, I analyse the interaction between the holm-oak Quercus ilex, and one of its main dispersers, the European jay Garrulus glandarius, in an heterogeneous Mediterranean landscape. I quantify the spatial dispersal pattern of the seed shadow at two spatial scales, landscape (among patches) and microhabitat (within patches), by directly tracking the movement of seeds. Two main traits of the jay-mediated dispersal of holm-oak acorns across the landscape, the spatial pattern of dissemination and the distance from the source tree, are significantly and directly influenced by jay activity. Jays moved acorns nonrandomly, avoiding one main patch type of the study area to cache acorns, the shrubland-grasslands, and moving most of the acorns to pine stands, whether afforestation or open pinewoods. Within each patch type, jays had also a strong preference for caching acorns in some microhabitats, since>95% of the acorns dispersed by jays were cached beneath pines. The distance of holm-oak acorn dispersal was long in the study site, over 250 m, with some dispersals occurring up to 1 km from the source oaks. The shape of the dispersal kernel function fitted to the dispersal pattern produced by jays differed from those quantified for many other plant species. Jay-mediated dispersal had two components, one local and another produced by long-distance dispersal. Due to the heterogeneity of these Mediterranean environments, this difference in scale overlaps with a difference in habitat composition, short distances events resulting in dispersals within the same oak stands and long distance events resulting in dispersal outside of oak stands, usually to other vegetation units. Jay activity and movement pattern can have thus dramatic effects on both the local regeneration as well as the potential for regional spread of the holm-oak populations.
Keywords: dispersal pattern; European jay (PG); Holm oak

Leaf fluctuating asymmetry of Holm oak in response to drought under contrasting climatic conditions - Hódar, José a. (Journal of Arid Environments, 2002)
Fluctuating asymmetry (FA) can be defined as small, random deviations from bilateral symmetry in structures that, typically, are bilaterally symmetrical. In plants, FA has been used as a tool for monitoring levels of ecological stress. In this work, I analyse the FA response to drought in the Holm oak (Quercus ilex) in SE Spain, to test whether FA increases or diminishes when climatic conditions are more stressful. Leaves from three different cohorts, corresponding to one drought year (1995) and two wet years (1996 and 1997) were collected at five sites contrasting in rainfall conditions, from very low to rather high rainfall. In two of the zones, two different morphs of leaves were collected. Furthermore, one of the sites was chosen close to a river, to examine the effect of water enhancement in the trees during drought and post-drought conditions. The results revealed no differences in response to drought in terms of FA between leaf morphs. However, while plants from rainy sites showed a decline in leaf FA from drought to wet years, the water-enhanced site and the dry sites showed scant or negligible differences between years. There was a significant decrease in FA from rainy sites to dry sites. These results suggest that (1) plants living in the more stressful sites are more symmetrical, (2) the more symmetrical plants respond less to yearly variations in drought stress, and (3) the response to yearly variations in drought depend on the climatic conditions in which a tree is living
Keywords: Drought; Fluctuating asymmetry; Holm oak; Mediterranean climate; Quercus ilex; RAINFALL

DETERMINACIÓN DE ROTACIONES ÓPTIMAS EN LA APLICACIÓN DE RESALVEOS DE CONVERSIÓN A MONTE ALTO EN TALLARES DE ENCINA Y DE QUEJIGO EN LA ZONA CENTRAL DE LA PENÍNSULA IBÉRICA. - BRAVO, J A; Sánchez, I; Serrada, R (III Congreso Forestal Español, 2001)
Conversion thinning seems to be a good option for most of the coppicce forests of holm oak and gall oak, where the lack of management is causing severe problems. Intensity and rotation of thinning are the two main parameters to be studied. This paper deals with the second one. Six coppicce forests of holm oak and two for gall oak in the Guadalajara province where selected. Those stands had been thinned in a known date, and have been compared with near control stands, which have not been thinned in the past. Diameter growth after thinning has been studied throught rings count and ring width measurement in both kind of stands. 129 trees of holm oak and 79 trees of gall oak have been studied. The main conclusions are the evidence of a significant growth of diameter in holm oaks that is present 11 years after the thinning, while in gall oak results are not so clear. In gall oak just one site showed a positive answer to thinning, that was present until 17 years after. K.W.:
Keywords: conversion thinning; coppicce forest; gall oak; Growth; Holm oak; rotation

DETERMINACIÓN DE ROTACIONES ÓPTIMAS EN LA APLICACIÓN DE RESALVEOS DE CONVERSIÓN A MONTE ALTO EN TALLARES DE ENCINA Y DE QUEJIGO EN LA ZONA CENTRAL DE LA PENÍNSULA IBÉRICA. - BRAVO, J. A.; SÁNCHEZ, I.; SERRADA, R. (III Congreso Forestal Español, 2001)
Conversion thinning seems to be a good option for most of the coppicce forests of holm oak and gall oak, where the lack of management is causing severe problems. Intensity and rotation of thinning are the two main parameters to be studied. This paper deals with the second one. Six coppicce forests of holm oak and two for gall oak in the Guadalajara province where selected. Those stands had been thinned in a known date, and have been compared with near control stands, which have not been thinned in the past. Diameter growth after thinning has been studied throught rings count and ring width measurement in both kind of stands. 129 trees of holm oak and 79 trees of gall oak have been studied. The main conclusions are the evidence of a significant growth of diameter in holm oaks that is present 11 years after the thinning, while in gall oak results are not so clear. In gall oak just one site showed a positive answer to thinning, that was present until 17 years after. K.W.:
The following values have no corresponding Zotero field: periodical: III Congreso Forestal Español issue: 1 pub-location: Granada
Keywords: conversion thinning; coppicce forest; gall oak; Growth; Holm oak; rotation

Fine-root longevity of Quercus ilex - López, B.; Sabate, S.; Gracia, C. A. (New Phytologist, 2001)
* • Fine-root longevity and phenology were studied in a Quercus ilex (holm oak) forest in Prades (NE Spain). Differences were investigated among roots that had appeared in different seasons and at different depth intervals, differentiating between white and brown roots. * • Using minirhizotrons installed in March 1994, 1211 roots were monitored every 3 wk from June 1994 to March 1997. * • Mean and median fine-root longevity were 125 ± 4 d and 67 d, respectively. Longevity of summer and winter roots was greater than that of spring and autumn roots. Although roots appeared and disappeared throughout the year, the rate of appearance was greatest in spring. Maximum longevity occurred at a soil depth of 20–30 cm. Differences among 10-cm depth intervals were due to the number of days that roots were brown, since roots remained white for a similar number of days, independent of soil depth. * • Temperate soil temperatures and lignotubers permitted the appearance of roots throughout the year. Holm oak fine roots might be more efficient during the first 50 d of their life before the white roots become less efficient brown roots.
The following values have no corresponding Zotero field: publisher: Blackwell Science Ltd
Keywords: Fine root longevity; Holm oak; minirhizotron; Quercus ilex; vertical longevity pattern

Fine-root longevity of Quercus ilex - López, B; Sabate, S; Gracia, C A (New Phytologist, 2001)
* • Fine-root longevity and phenology were studied in a Quercus ilex (holm oak) forest in Prades (NE Spain). Differences were investigated among roots that had appeared in different seasons and at different depth intervals, differentiating between white and brown roots. * • Using minirhizotrons installed in March 1994, 1211 roots were monitored every 3 wk from June 1994 to March 1997. * • Mean and median fine-root longevity were 125 ± 4 d and 67 d, respectively. Longevity of summer and winter roots was greater than that of spring and autumn roots. Although roots appeared and disappeared throughout the year, the rate of appearance was greatest in spring. Maximum longevity occurred at a soil depth of 20–30 cm. Differences among 10-cm depth intervals were due to the number of days that roots were brown, since roots remained white for a similar number of days, independent of soil depth. * • Temperate soil temperatures and lignotubers permitted the appearance of roots throughout the year. Holm oak fine roots might be more efficient during the first 50 d of their life before the white roots become less efficient brown roots.
Keywords: Fine root longevity; Holm oak; minirhizotron; Quercus ilex; vertical longevity pattern

Morphometric and biochemical contributions to the structuration and systematics of the Holm oak Quercus ilex L. specific complex - Lebreton, P; Barbero, M; Quezel, P (ACTA BOTANICA GALLICA, 2001)
The ecological amplitude and the biological variability of the Holm oak are such that any systematic characterization is hazardous. This study, conducted from eleven origins representative of the Western Mediterranean area, is novel by its pluridisciplinary and statistical approach. Chemical (foliar flavonoids) and morphometric data (dry weight, lengthening, veins of the leaves) support the same conclusion that the ``variability{''} of the Holm oak is structured by Ford sensu polymorphism. The distinction between ilex and rotundifolia remains pertinent from a first order perspective, but the second taxon should also be sub-divided into two distinct entities, the first in the Iberian peninsula, the other in North Africa. We consider the Holm oak as a specific complex comprising three taxa: ilex L.; rotundifolia emend. and maghrebiana subsp. nov. Although the Pyrenees constituted a barrier between ilex and rotundifolia, hybridisations and mutual introgressions doubtless explain certain abnormalities in Catalonia and Languedoc, A primarily morphometric determination key is proposed, though to be entirely rigorous only a population-based and multivariate-based approach, with inclusion of the biochemical parameters, can hope to address with sufficiently subtlety a problem of this complexity.
Keywords: Holm oak; Polymorphism; systematics

Non-steady-state modelling of water transfer in a Mediterranean evergreen canopy - Lhomme, J. P.; Rocheteau, A.; OURCIVAL, J. M.; Rambal, S. (Agricultural and Forest Meteorology, 2001)
A model simulating the diurnal pattern of water transfer within a Holm oak (Quercus ilex) canopy in Mediterranean conditions has been designed. It combines a non-steady-state hydraulic model with a transpiration model. The hydraulic model includes a reservoir represented by a capacitance, a soil–plant hydraulic resistance and a storage hydraulic resistance connected to the capacitance. It simulates the diurnal variation of water uptake and storage ﬂow from the diurnal course of transpiration used as input. The transpiration model is based upon the Penman–Monteith equation and a Jarvis-type representation of the stomatal resistance (i.e., a minimum stomatal resistance multiplied by the product of independent stress functions). Simultaneous measurements of canopy evaporation by an eddy covariance system and water uptake from the soil by sap ﬂow measurements have allowed one to calibrate and validate the model. The capacitance has been found to be equal to 0.17 mm MPa−1 (with a storage hydraulic resistance of about 2 MPa h mm−1 ), generating a time lag of about 1 h between the transpiration rate and the water uptake from the soil. The hydraulic model correctly represents the experimental data. The transpiration model provides reasonable estimates, but with a signiﬁcant scatter. The combined model simulates the diurnal variation of water uptake, storage ﬂow and transpiration rate directly from environmental variables, but in this latter case, the storage ﬂow is estimated with a rather poor accuracy
Keywords: Capacitance; Holm oak; Hydraulic resistance; Non-steady-state model; stomatal resistance; Transpiration; Water storage; Water uptake

REFORESTACIÓN DE TIERRAS AGRARIAS CON ENCINA Y COSCOJA. UN CASO EN TOLEDO - BARREDA, A; SOBRINI, I (III Congreso Forestal Español Congreso, 2001)
The Holm Oak (Quercus ilex) and the Kermes Oak (Quercus coccifera), both together, are being used successfuly in the dry Spain in the afforestations made under the Afforestation of Agricultural Land European Program, since 1993. We study a 1998/1999 afforestation of a farm in Toledo, in two pieces of 50 ha. each, until that moment dedicated to dry farming grain crops. The slopeswere between 0 and 10%, with sandy soils. All the farm presents high density of small game species. The results obtained, with less than 8% faults after two years, under conditions of little rain in 1998/99, and very dry summer in 2000, answer for the afforestation method employed, and permit us recomend it for other farms.
Keywords: Agricultural land; dry regions; Holm oak; Kermes Oak

REFORESTACIÓN DE TIERRAS AGRARIAS CON ENCINA Y COSCOJA. UN CASO EN TOLEDO - BARREDA, A.; SOBRINI, I. (III Congreso Forestal Español Congreso, 2001)
The Holm Oak (Quercus ilex) and the Kermes Oak (Quercus coccifera), both together, are being used successfuly in the dry Spain in the afforestations made under the Afforestation of Agricultural Land European Program, since 1993. We study a 1998/1999 afforestation of a farm in Toledo, in two pieces of 50 ha. each, until that moment dedicated to dry farming grain crops. The slopeswere between 0 and 10%, with sandy soils. All the farm presents high density of small game species. The results obtained, with less than 8% faults after two years, under conditions of little rain in 1998/99, and very dry summer in 2000, answer for the afforestation method employed, and permit us recomend it for other farms.
The following values have no corresponding Zotero field: periodical: III Congreso Forestal Español Congreso pub-location: Granada
Keywords: Agricultural land; dry regions; Holm oak; Kermes Oak

The breakdown of leaves of poplar and holm oak in three Moroccan streams : effect of burial in the sediment - Naamane, B; Chergui, H; Pattee, E (Annales de Limnologie - International Journal of Limnology, 1999)
Weight loss of leaves of Populus nigra and Quercus ilex was observed in coarse-mesh bags exposed in three watercourses and their sediment (-30 and -50 cm) near the city of Fes. The watercourses were: Oued Sebou (a river), Oued Sidi-Harazem (issuing from a warm spring), and Ain Chkef (a cold spring). Weight loss was faster at the surface than within the sediment. Weight loss was faster in poplar than in the tough holm oak leaves. At all levels, weight loss was fastest in Oued Sebou where the water flowed faster both at the surface and within the coarser sediment. It was slowest in the cold spring. Thus the influence of leaf texture, current velocity, and temperature were stressed
Keywords: burial; decomposition; Holm oak; Poplar; watercourse

Breeding performance of the Blue Tit Parus caeruleus in a patchy Mediterranean landscape - Catalan, R M; Haeger, J F (REVUE D ECOLOGIE-LA TERRE ET LA VIE, 1999)
This study compares reproductive strategy and breeding success of Parus caeruleus in a helm-oak (Quercus rotundifolia) forest and a pine plantation (Pinus pinea and P. pinaster) in the southern Iberian Peninsula. During the breeding period, an asymmetric flow of individuals takes place from the helm-oak forest to the pine plantation. This flow is favoured by nestboxes where Blue tits can lay their eggs. During the winter, a large part of the population moves back from the pine plantation to the helm-oak forest. Breeding pair density was much higher in the helm-oak forest than in the pine plantation. This may bt accounted for by the poorer quality of the resources available in the pine plantation which birds try to compensate for with larger breeding territories. Breeding density and most life-history traits examined (timing of breeding, clutch site, egg size, number of fledglings and fledgling weight) were similar in both habitats, as a result of the phenotypic plasticity of this species. Although breeding success was similar in both habitats, recruitment of new individuals per unit area was higher in the helm-oak forest. The consequences of pine plantations, as a form of forestry management, on species conservation is discussed.
APS
Keywords: breeding success; Holm oak; iberian peninsula; Parus caeruleus; Pinus pinaster; Pinus pinea; Quercus ilex; reproductive strategies

Diurnal changes in antioxidant and carotenoid composition in the Mediterranean schlerophyll tree Quercus ilex(L) during winter - García-Plazaola, J. I.; Artetxe, Unai; BECERRIL, J. M.; Garcı, Ignacio (Plant Science, 1999)
Seasonal changes of pigment composition and antioxidant content were characterized in the Mediterranean evergreen holm oak (Quercus ilex L.). Higher contents of antioxidants and carotenoids, with a photoprotective role during winter, indicated that this period was highly stressful, so a study of diurnal changes in photosynthesis, pigments and carotenoids was conducted during January in sun and shade leaves. Sun and shade leaves were used to compare the effects due only to low temperature separate from those resulting from the interaction of light. During winter, a relatively high rate of CO2 ﬁxation on sun leaves represented an important sink for photosynthetic electrons contributing to the annual carbon balance of the plant. This high rate contrasted with a reduced Fv :Fm, even at predawn. This reduction was correlated with the accumulation of zeaxanthin at the expense of violaxanthin by de-epoxidation. Sun leaves were also protected by a higher concentration of antioxidants (ascorbate, glutathione and tocopherol) and carotenoids (except lutein epoxide). Ascorbate was 10–50-fold greater than the other antioxidants, indicating a central role in protection against photooxidative stress. Nevertheless those mechanisms were unable to avoid a loss of hydrophilic antioxidants (glutathione and ascorbate) and xanthophylls during the initial morning hours after dawn, indicating that the ﬁrst target of photooxidative damage was these molecules
Keywords: Holm oak; low-temperature stress; Mediterranean evergreens; photoinhibition; photoprotection; xanthophyll cycle

Diurnal changes in antioxidant and carotenoid composition in the Mediterranean schlerophyll tree Quercus ilex(L) during winter - Garcia-Plazaola, J I; Artetxe, Unai; BECERRIL, J M; Garcı, Ignacio (Plant Science, 1999)
Seasonal changes of pigment composition and antioxidant content were characterized in the Mediterranean evergreen holm oak (Quercus ilex L.). Higher contents of antioxidants and carotenoids, with a photoprotective role during winter, indicated that this period was highly stressful, so a study of diurnal changes in photosynthesis, pigments and carotenoids was conducted during January in sun and shade leaves. Sun and shade leaves were used to compare the effects due only to low temperature separate from those resulting from the interaction of light. During winter, a relatively high rate of CO2 ﬁxation on sun leaves represented an important sink for photosynthetic electrons contributing to the annual carbon balance of the plant. This high rate contrasted with a reduced Fv :Fm, even at predawn. This reduction was correlated with the accumulation of zeaxanthin at the expense of violaxanthin by de-epoxidation. Sun leaves were also protected by a higher concentration of antioxidants (ascorbate, glutathione and tocopherol) and carotenoids (except lutein epoxide). Ascorbate was 10–50-fold greater than the other antioxidants, indicating a central role in protection against photooxidative stress. Nevertheless those mechanisms were unable to avoid a loss of hydrophilic antioxidants (glutathione and ascorbate) and xanthophylls during the initial morning hours after dawn, indicating that the ﬁrst target of photooxidative damage was these molecules
Keywords: Holm oak; low-temperature stress; Mediterranean evergreens; photoinhibition; photoprotection; xanthophyll cycle

Etiology of oak decline in Spain - Gallego, F J; de Algaba, A Perez; Fernandez-Escobar, R (European Journal of Forest Pathology, 1999)
In different areas of Extremadura, Western Spain, soil samples were taken at the bottom of holm oak (Quercus ilex) trees that were showing decline symptoms. Half of each sample was sterilized, and acorns were sown in both sterilized and nonsterilized soil samples. The resulting seedlings were used as baits for the isolation of fungi. Seedlings growing on the natural, nonsterilized substrate were characterized by having a lower vegetative growth than the ones growing on the sterilized soil samples, and most of them died. Phytophthora dnnamomi was consistently isolated from their roots. Fusarium oxysporum was also isolated as well as different species of Pythium, although to a lesser extent. Pathogenicity tests were performed on holm oak seedlings with five different isolates of P. chinnamomi, with F. oxysporum, Pythium and with a mixture of the three fungi. All the inoculated seedlings with P. chinnamomi developed root rot and grew slowly, and 35.7% of them died up to the end of the experiments. P. chinnamomi was consistently isolated from their roots, indicating that this fungus is the causal agent of holm oak decline. However, F. oxysporum caused similar symptoms on oak seedlings as P. chinnamomi, and was isolated also from the roots, although its frequency was lower than that of. P. cinnamomi.
Keywords: Holm oak; Oak decline; Pathogenicity; Phytophthora cinnamomi (PG)

Etiology of oak decline in Spain - Gallego, F. J.; de Algaba, A. Perez; Fernandez-Escobar, R. (European Journal of Forest Pathology, 1999)
In different areas of Extremadura, Western Spain, soil samples were taken at the bottom of holm oak (Quercus ilex) trees that were showing decline symptoms. Half of each sample was sterilized, and acorns were sown in both sterilized and nonsterilized soil samples. The resulting seedlings were used as baits for the isolation of fungi. Seedlings growing on the natural, nonsterilized substrate were characterized by having a lower vegetative growth than the ones growing on the sterilized soil samples, and most of them died. Phytophthora dnnamomi was consistently isolated from their roots. Fusarium oxysporum was also isolated as well as different species of Pythium, although to a lesser extent. Pathogenicity tests were performed on holm oak seedlings with five different isolates of P. chinnamomi, with F. oxysporum, Pythium and with a mixture of the three fungi. All the inoculated seedlings with P. chinnamomi developed root rot and grew slowly, and 35.7% of them died up to the end of the experiments. P. chinnamomi was consistently isolated from their roots, indicating that this fungus is the causal agent of holm oak decline. However, F. oxysporum caused similar symptoms on oak seedlings as P. chinnamomi, and was isolated also from the roots, although its frequency was lower than that of. P. cinnamomi.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Holm oak; Oak decline; Pathogenicity; Phytophthora cinnamomi (PG)

Holm oak and holm oak forests: An introduction - Terradas, J (Ecology of Mediterranean Evergreen Oak Forests, 1999)
Why should we study the Mediterranean evergreen forests of holm oak (Quercus ilex L.)? Besides the pursuit of knowledge, two major reasons can be put forward. First, holm oak forests are a dominant type of vegetation in a transition zone between temperate forests, mostly dominated by deciduous trees and the scrublands (maquis, chaparral, phrygana, etc.) that herald the tropical regions. In this transition zone, plants have had to cope with a selective pressure resulting from a double stress - winter cold and summer drought - that has determined their morphological and ecophysiological evolutive responses. One of our aims is to provide an insight into the features of holm oak as related to environmental factors and in comparison with other tree types (broadleaved deciduous hardwoods, needle-leafed conifers)
APS
Keywords: Geral; Holm oak; Mediterranean; Quercus ilex

Herbivory affects developmental instability of stone oak, Quercus rotundifolia - Moller, A P; de Lope, F (OIKOS, 1998)
The effects of herbivory on plant fitness have traditionally been assessed by reductions in performance measured in terms of physiological, growth, and reproductive parameters. We investigated the direct effect of herbivory on a measure of foliar developmental instability (fluctuating asymmetry in leaf width) in evergreen stone oak. Quercus rotundifolia. Since leaves from more than a single growth season are present simultaneously, it is possible to compare measures of developmental instability of newly formed leaves in relation to the extent of herbivory in the previous season as assessed from damage to old leaves. We found significantly increased asymmetry in leaf width when leaves From the previous year showed signs of herbivory. This result was confirmed experimentally by using leaf removal to mimic herbivory. Oak trees where many old leaves were removed had increased foliar asymmetry compared to oak trees where only few leaves had been removed and untreated control trees. Using foliar asymmetry in old leaves from the previous year as a baseline for these comparisons confirmed that foliar asymmetry of individual trees increased as a consequence of herbivory. Oak trees with high degrees of asymmetry were more likely to die than oak trees with low asymmetry. These results suggest that foliar asymmetry is symptomatic of a stressed plant. Herbivores can both produce such a stress, leading to increased asymmetry, and attack differentially more asymmetric plants. In the extreme, the most asymmetric plants are those most likely to die.
APS
Keywords: foliar asymmetry; herbivory essect; Holm oak; plant fitness

Light and temperature dependence of the emission of cyclic and acyclic monoterpenes from holm oak (Quercus ilex L.) leaves - Staudt, M; Bertin, N (Plant, Cell & Environment, 1998)
In a laboratory study, we investigated the monoterpene emissions from Quercus ilex, an evergreen sclerophyllous Mediterranean oak species whose emissions are light dependent. We examined the light and temperature responses of individual monoterpenes emitted from leaves under various conditions, the effect of heat stress on emissions, and the emission-onset during leaf development. Emission rate increased 10-fold during leaf growth, with slight changes in the composition. At 30 °C and saturating light, the monoterpene emission rate from mature leaves averaged 4·1 nmol m–2 s–1, of which α-pinene, sabinene and β-pinene accounted for 85%. The light dependence of emission was similar for all monoterpenes: it resembled the light saturation curve of CO2 assimilation, although monoterpene emission continued in the dark. Temperature dependence differed among emitted compounds: most of them exhibited an exponential increase up to 35 °C, a maximum at 42 °C, and a slight decline at higher temperatures. However, the two acyclic isomers cis-β-ocimene and trans-β-ocimene were hardly detected below 35 °C, but their emission rates increased above this temperature as the emission rates of other compounds fell, so that total emission of monoterpenes exponentially increased from 5 to 45 °C. The ratio between ocimene isomers and other compounds increased with both absolute temperature and time of heat exposure. The light dependence of emission was insensitive to the temperature at which it was measured, and vice versa the temperature dependence was insensitive to the light regime. The results demonstrated that none of the models currently applied to simulate isoprene or monoterpene emissions correctly predicts the short-term effects of light and temperature on Q. ilex emissions. The percentage of fixed carbon lost immediately as monoterpenes ranged between 0·1 and 6·0% depending on temperature, but rose up to 20% when leaves were continuously exposed to temperatures between 40 and 45 °C.
Keywords: biogenic VOC emission; emission model; heat stress; Holm oak; Isoprenoids; light effect; Monoterpenes; Quercus ilex; temperature effect

O3 AND 03+C02 EFFECTS ON A MEDITERRANEAN EVERGREEN BROADLEAF TREE, HOLM OAK (QUERCUS iLEX L.) - Manes, F; Vitale, M; Donato, E; Paoletti, E (Chemosphere, 1998)
The aim of this work is to analyze the effects of a) short-term treatments with different concentrations of 0, (daily 6-hour fumigation with 0, 65, 175 and 300 ppb for 3-4 days); and 6) a medium term treatment with O9 (150 ppb three times a week for thirty days on the whole) and CO2 (700 ppm) on gas exchange, chlorophyll fluorescence, and peroxidase activity in holm oak (Quercus ilex L.) leaves. The results show that net photosynthesis, transpiration, Fv/Frvr ratio and POD activity were not influenced until an O1 concentration of 300 ppb was reached. At this threshold, significant alterations in these physiological and biochemical parameters were found. The treatment with +C02 +O, showed an increase of net photosynthesis suggesting thus an antagonistic effect of CO2 with regard to Oj-induced injuries, while CO2 alone increased photosynthesis and decreased transpiration but induced no effects on FV/‘F, ratio or peroxidase activity. From our data, holm oak shows a resistance to episodes ofphotochemical 0, stress, that in the Mediterranean region can reach peaks of > 100 ppb. This response is likely to be due to the morpho-anatomic structure of helm oak leaves and their sclerophyllous adaptations. This might leads helm oak to adopt a stress tolerance strategy with regard to leaf response to O,, the effects of which cannot be ameliorated by an increase of atmospheric CO2
Keywords: CO2 (voyant); Holm oak; Net photosynthesis; ozone exposure; peroxidase activity; Transpiration

Photosynthesis and photoprotection in Quercus ilex resprouts after fire - Fleck, I; Hogan, K P; Llorens, L; Abadía, A; Aranda, X (Tree Physiology, 1998)
Plants that resprout after fires often have higher rates of photosynthesis than before a fire. To elucidate the mechanism of this response, we studied gas exchange and chlorophyll fluorescence in Quercus ilex L. plants growing on control (unburned) sites and on sites that had been burned the preceding summer. In early July, photosynthetic rates and stomatal conductance were similar in plants on unburned and burned plots, and in young and old foliage within unburned plots. At this time, photochemical efficiency of photosystem II (PSII), nonphotochemical quenching of chlorophyll fluorescence (NPQ), and the de-epoxidation of violaxanthin to zeaxanthin were also similar among leaves of different ages and treatments. In late July, photosynthetic rates and stomatal conductances were much greater in resprouts on the burned areas than in unburned plants. From early to late July, unburned plants showed an increase in NPQ and the de-epoxidation of violaxanthin to zeaxanthin, indicating increased photoprotection as a result of enhanced nonradiative dissipation of excess light energy. Plants on the burned plots did not show these changes. Leaves of all ages and treatments showed no substantial reduction in potential quantum yield of PSII (Fv/Fm) at midday or predawn, indicating that there was little or no photoinhibition. Leaf nitrogen and soluble protein contents varied with leaf age during July, but did not vary between treatments. We conclude that the primary effect of burning is an increase in water availability to resprouting plants that eliminates the need for photoprotection, at least in the short term. The decrease in photosynthetic rates of unburned leaves in late July was the result of reduced stomatal conductance. We suggest that lowered stomatal conductance is the primary limiting factor in Q. ilex leaves, governing the regulation of carboxylation activity and energy dissipation processes.
10.1093/treephys/18.8-9.607
Keywords: chlorophyll fluorescence; Gas exchange; Holm oak; photoinhibition; Photosystem II; zeaxanthin

Stemflow and throughfall determination in a resprouted Mediterranean holm-oak forest - Bellot, Juan; Escarre, Antonio (Ann. For. Sci., 1998)
Stemflow, throughfall and precipitation data were collected for 30 consecutive months in a holm-oak forest dominated by Quercus ilex, Arbutus unedo and Phyllirea media. These flux data were obtained from 50 randomly distributed no-roving throughfall collectors and 20 stemflow measuring devices (ten on Q. ilex and five on each of the other species). The stemllow was highly influenced by tree size and amount of rainfall, showing a significant correlation for each tree. Throughfall results showed a high spatial variability for each storm, with a significant independence of collectors. At forest scale, stemflow and throughfall represented 12.1 and 75 % of precipitation, respectively, and interception was estimated as 12.9 % of precipitation. Partitioning of rainfall between stemflow and throughfall created a high spatial heterogeneity of water distribution under the canopy. Stemflow increased more than 30 times the mean amount of water received per unit soil area around tree trunks. Finally, the effect of a change in the amount of precipitation according to a regional scenario was analyzed. It was shown that the increase in high rainfall events rather than small events increased the stemflow percentage.
Keywords: Holm oak; interception; spatial heterogeneity; stemflow; throughfall

Stemflow and throughfall determination in a resprouted Mediterranean holm-oak forest - Bellot, Juan; Escarre, Antonio (Ann. For. Sci., 1998)
Stemflow, throughfall and precipitation data were collected for 30 consecutive months in a holm-oak forest dominated by Quercus ilex, Arbutus unedo and Phyllirea media. These flux data were obtained from 50 randomly distributed no-roving throughfall collectors and 20 stemflow measuring devices (ten on Q. ilex and five on each of the other species). The stemllow was highly influenced by tree size and amount of rainfall, showing a significant correlation for each tree. Throughfall results showed a high spatial variability for each storm, with a significant independence of collectors. At forest scale, stemflow and throughfall represented 12.1 and 75 % of precipitation, respectively, and interception was estimated as 12.9 % of precipitation. Partitioning of rainfall between stemflow and throughfall created a high spatial heterogeneity of water distribution under the canopy. Stemflow increased more than 30 times the mean amount of water received per unit soil area around tree trunks. Finally, the effect of a change in the amount of precipitation according to a regional scenario was analyzed. It was shown that the increase in high rainfall events rather than small events increased the stemflow percentage.
Keywords: Holm oak; interception; spatial heterogeneity; stemflow; throughfall

UV-band and acid rain effects on beach ( Fagus sylvatica L.) and holm oak ( Quercus ilex L.) leaves - Paoletti, E (Chemosphere, 1998)
Beech (Fagus sylvatica L.) and holm oak (Quercus ilex L) leaves were subjected to simulated acid rain and UV-B radiation for 10 days. The almost glabrous beech leaves revealed a greater predisposition to developing macroscopic necrotic lesions than the pubescent holm oak leaves. This response is due primarily to their different morpho-anatomical structure, rather than to a difference in the synthesis of UV-B absorbing pigments (flavonoids); the response was also accompanied by microscopically observable alterations (collapse of epidermal cells, fusion of surface wax structures, structural damage to the stomata) and by the reduction of stomatal conductance
Keywords: acid rain; beech; damage; Holm oak; leaves; necrosis; stomatal conductance (voyant); uv-b radiation

Variability in seedling water status during drought within a Quercus ilex subsp. ballota population, and its relation to seedling morphology - Leiva, María José; Fernández-Alés, Rocı́o (Forest Ecology and Management, 1998)
Differences in morphology, growth and plant water status during drought were studied in greenhouse-grown Quercus ilex subsp. ballota seedlings produced by different mother trees occurring in a savannah-like forest (locally named dehesa) in southern Spain. There were signi®cant differences among mother trees in the biomass of their seeds (mother tree level accounted for 62% of total variance in this trait), in the percentage of seedlings that emerged and in the time of shoot emergence. The progeny that had high emergence rates (80±90%) also had short emergence times while the opposite was true for the progeny that had low (43%) and intermediate (70%) emergence rates. Acorn biomass covaried signi®cantly with seedling total biomass and with the biomass of different parts of the seedlings, but not with the partitioning of biomass among roots and shoots (root/shoot ratio) nor to morphological seedling traits such as shoot height, total leaf area, average leaf size, speci®c leaf area (SLA) and leaf number. All these traits varied signi®cantly among the seedlings produced by different mother trees. The conductance to water vapour (glw) of the foliage of the seedlings also varied signi®cantly among mother trees and was dependent on the root/shoot ratio as on the total leaf area of the seedlings, but not on the total seedling biomass. One of the six trees that were studied produced seedlings which had a signi®cantly higher root/shoot ratio, smaller leaf area, smaller leaves, higher speci®c leaf area and shorter stems than the seedlings produced by any other tree. In addition, the former set of seedlings had signi®cantly higher glw 15 and 30 days after drought, and higher leaf water content at the end of the experiment than the other seedlings. We discuss the value of using single seedling traits related to drought tolerance such as root/shoot ratio and leaf area in the framework of the restoration of savannah-like oak forest in the Mediterranean areas. We also discuss the functional implications of the diversity of genotypes within the oak populations in the framework of the global climate change
Keywords: Drought tolerance; Holm oak; root/shoot ratio; savannah-like forest; seedling biomass

Adaptation and local validation in a Mediterranean environment of a process-level ecosystem model driven by remotely sensed inputs - Lacaze, B; Tabarant, F; Rambal, S (REMOTE SENSING `96: INTEGRATED APPLICATIONS FOR RISK ASSESSMENT AND DISASTER PREVENTION FOR THE MEDITERRANEAN, 1997)
A process-level ecosystem model (FOREST-BGC) has been used to simulate the short-term variability of functional processes and the slower responding allocation of photosynthesis products to plant components maintenance or growth, and to decomposition. The model emphasises Leaf Area Index (LAI) as a key structural attribute with substantial control over ecosystem process rates. Model simulations (soil water balance, photosynthesis, net primary production,...) have been obtained for a 10 years period (1984-1993) and partially validated with ground measurements from an experimental test site located in Southern France (dominant species: holm oak). Further work include scaling up from local to regional level, using remote sensing inputs and ancillary data.
Keywords: funtional processes; Holm oak; leaf area index; model simutalins; photosynthesis alocation; structural attribute

Diurnal and seasonal course of monoterpene emissions from Quercus ilex(L.) under natural conditions application of light and temperature algorithms - Bertin, N.; Staudt, M.; Hansen, U.; Seufert, G.; Foster, P.; Fugit, J. L.; Torres, L. (Atmospheric Environment, 1997)
Quercus ilex is a common oak species in the Mediterranean vegetation and a strong emitter of monoterpenes. Since the short-term control of monoterpene emissions from this species involved both temperature and light, the usual exponential function of temperature may not be sufficient to model the diurnal and seasonal emission course. In the frame of the BEMA-project (Biogenic Emissions in the Mediterranean Area), we investigated the tree-to-tree, branch-to-branch, diurnal, and seasonal variability of monoterpene emissions from Q. ibex over one and a half years at Castelporziano (Rome, Italy). In addition, w,: checked the suitability of the model developed for isoprene by Guenther et al. (1991, 1993) to simulate the short- and long-term variations of monoterpene emissions from this particular species. We found that the tree-to-tree variability was rather small compared to the experimental error during air sampling and analysis by diverse laboratories. The branch-to-branch variability was noticeable between sun- and shade-adapted branches only. 80% of total emissions were represented by cc-pinene, B-pinene and sabinene, whose proportions were stable over the year and independent of light exposure. The emission factor (emission rate at 30°C and 1000 ~molphotonm-Zs-l ) estimated by the isoprene model or extrapo- lated from measurements was similar: it was about 22 pggdw -r h-r for sun-exposed branches and 2.3 pggdw.-’ h-r for shade-adapted branches. It was rather stable over the seasons except during leaf development. The diurnal and seasonal emission patterns from Q. ibex were simulated in a satisfying way by Guenther’s algorithms especially if we excluded the laboratory variability. For shade-adapted branches, an emission factor 17 times lower had to be applied, but temperature and light responses were unchanged.
Keywords: Holm oak; index; light and temperature algorithm; Mediterranean vegetation; Modelling; Monoterpene; Quercus ilex

Diurnal and seasonal course of monoterpene emissions from Quercus ilex(L.) under natural conditions application of light and temperature algorithms - Bertin, N; Staudt, M; Hansen, U; Seufert, G; Foster, P; Fugit, J L; Torres, L (Atmospheric Environment, 1997)
Quercus ilex is a common oak species in the Mediterranean vegetation and a strong emitter of monoterpenes. Since the short-term control of monoterpene emissions from this species involved both temperature and light, the usual exponential function of temperature may not be sufficient to model the diurnal and seasonal emission course. In the frame of the BEMA-project (Biogenic Emissions in the Mediterranean Area), we investigated the tree-to-tree, branch-to-branch, diurnal, and seasonal variability of monoterpene emissions from Q. ibex over one and a half years at Castelporziano (Rome, Italy). In addition, w,: checked the suitability of the model developed for isoprene by Guenther et al. (1991, 1993) to simulate the short- and long-term variations of monoterpene emissions from this particular species. We found that the tree-to-tree variability was rather small compared to the experimental error during air sampling and analysis by diverse laboratories. The branch-to-branch variability was noticeable between sun- and shade-adapted branches only. 80% of total emissions were represented by cc-pinene, B-pinene and sabinene, whose proportions were stable over the year and independent of light exposure. The emission factor (emission rate at 30°C and 1000 ~molphotonm-Zs-l ) estimated by the isoprene model or extrapo- lated from measurements was similar: it was about 22 pggdw -r h-r for sun-exposed branches and 2.3 pggdw.-’ h-r for shade-adapted branches. It was rather stable over the seasons except during leaf development. The diurnal and seasonal emission patterns from Q. ibex were simulated in a satisfying way by Guenther’s algorithms especially if we excluded the laboratory variability. For shade-adapted branches, an emission factor 17 times lower had to be applied, but temperature and light responses were unchanged.
Keywords: Holm oak; index; light and temperature algorithm; Mediterranean vegetation; Modelling; Monoterpene; Quercus ilex

Estudio comparativo de morfología en planta de encina cultivada en distintos envases comerciales - ÁLVAREZ LINAREJOS, L; RAPP ARRARÁS, I (II Congreso Forestal Español, 1997)
The aim of the present work is to analize the morfological diferences and its caracterization depending on the container used in nursery production of one year holm oak plants. Six different types of containers -those suitable to be bought in the area were the experiment has taken place- has been used for it. It has been stablished the greatest posible homogeneity in other parameters which influence could have been important such as seeds - which procedence is known-, cultivation media, watering, and microclimate -in greenhouse first and nursery later-. Results for sorne of the factors studied are shown.
Keywords: Containers; Holm oak; Nursery; Plant production

Estudio comparativo de morfología en planta de encina cultivada en distintos envases comerciales - ÁLVAREZ LINAREJOS, L.; RAPP ARRARÁS, I. (II Congreso Forestal Español, 1997)
The aim of the present work is to analize the morfological diferences and its caracterization depending on the container used in nursery production of one year holm oak plants. Six different types of containers -those suitable to be bought in the area were the experiment has taken place- has been used for it. It has been stablished the greatest posible homogeneity in other parameters which influence could have been important such as seeds - which procedence is known-, cultivation media, watering, and microclimate -in greenhouse first and nursery later-. Results for sorne of the factors studied are shown.
The following values have no corresponding Zotero field: periodical: II Congreso Forestal Español issue: 57 pub-location: Pamplona
Keywords: Containers; Holm oak; Nursery; Plant production

Estudo de germinação em azinheira (Quercus rotundifolia Lam.) - Ribeiro, M M A; Elvas, P S (I Congresso Florestal Hispano-Luso, 21 a 27 Junho 1997. Pamplona, 1997)
In April 1996 a germination trial took place in Serra da Malcata Natural Reserve nursery. The acorns were collected in Malpica do Tejo holm oak stands, after fruit repining. Treatments included naked root plant production in normal nursery soil and plant production with different other methods: two different containers (plastic bag and plastic pot) with five different media composition (pine bark, peat, normal nursery soil, pine bark with perlite (1:1 v/v) and peat with perlite (1:1 v/v). The number of germinated seeds (G) per treatment and block was first recorded by the end of June and afterwards three times, every three weeks. Last time data was recorded, the following parameters were included: diameter (D) at soil level, height (H) and the leaf area (A), per plant. Percent of germination was better in every treatment using plastic pots, whatever the media used, and the worst results were achieved with the plastic bag/peat and naked root methods. On the other hand, the use of the plastic bag promoted plant loss, avoided with plastic pots. The best-scored treatments for the average plant diameter (D) were the pot/peat (3,26 mm) and bag/pine bark (2,92 mm) methods, and the bag/nursery soil produced the worst result (2,4 mm). The best/worst result in the mean height for plant (H), was obtained with the naked root (10,5 cm)/plastic pot with nursery soil (5,9 cm) method. The leaf area per plant (A) was 52 cm2 for the naked root method, higher then the value of this parameter in every other treatment, except in the bag/pine bark one (45 cm2 ).
Keywords: container; germination; Holm oak; media; naked root; Quercus rotundifolia Lam

Influencia de los tratamientos selvícolas destinados a optimizar el desarrollo de QUERCUS ILEX SSP. BALLOTA BAJO LA CUBIERTA DE PINARES DE REPOBLACIÓN - ALVAREZ LINAREJOS, LAURA; ALEJANO MONGE, REYES; MADRIGAL COLLAZO, ALBERTO MARTÍNEZ MONTES, ENRIQUE; RApp ARRARÁS, ÍGOR (II Congreso Forestal Español, 1997)
Results about variables with important influence in the evolution of holm oak seedlings planted under pine trees covert, are shown in this work. These results come as part of a large experience placed in the Filabres Mountains, in Almería, Spain. Relations among the answer of the holm oaks studied, the pine forest -in which different intensity thinnings has been done- and different soil variables -meassured in the field plots- are searched.
Keywords: broadleaves sylviculture; Holm oak; mixed forest; oak sylviculture; thinnings

PLANTACIÓN Y SIEMBRA DE Quereus ilex L.: EFECTOS DE LA PREPARACIÓN DEL TERRENO Y DE LA UTILIZACIÓN DE PROTECTORES EN LA SUPERVIVENCIA DE PLANTAS - Ambiente, Ministerio D E Medio; NICOLÁS PERAGÓN, J L; DOMÍNGUEZ LERENA, S; HERRERO SIERRA, N; VILLAR- SALVADOR, P (II Congreso Forestal Español, 1997)
In a first experiment the effect of two tillage treatments, a deep mechanical tillage and no tillage, on the survival of seeded Quercus ilex seedlings was analysed. In a second experiment the influence of acorn seeding versus plantation of containerized seedling, as well as the effect of two types of treeshelters (with and without lateral ventilation holes) and treeshelter removal in summer on the survival of Q. ilex seedlings was studied. Microclimate inside treeshelters containing seedlings was also measured along a typical summer day. Deep tillage increased germination and survival in comparison with untilled treatment. Temperature and leaf to air vapor pressure deficit was higher inside the treeshelters, specially in those without wholes, than outside. In spite of this fact, both treeshelter types, and particularIy those with lateral ventilation holes, exhibited a higher survival percentages than the control without treeshelter. Neither acorn seeding nor the removal of treeshelters in summer improved survival. significantly.
Keywords: Acorn seeding; Holm oak; microclimate; Reforestation; Tillage

PLANTACIÓN Y SIEMBRA DE Quereus ilex L.: EFECTOS DE LA PREPARACIÓN DEL TERRENO Y DE LA UTILIZACIÓN DE PROTECTORES EN LA SUPERVIVENCIA DE PLANTAS - Ambiente, Ministerio D. E. Medio; NICOLÁS PERAGÓN, J. L.; DOMINGUEZ LERENA, S.; HERRERO SIERRA, N.; VILLAR- SALVADOR, P. (II Congreso Forestal Español, 1997)
In a first experiment the effect of two tillage treatments, a deep mechanical tillage and no tillage, on the survival of seeded Quercus ilex seedlings was analysed. In a second experiment the influence of acorn seeding versus plantation of containerized seedling, as well as the effect of two types of treeshelters (with and without lateral ventilation holes) and treeshelter removal in summer on the survival of Q. ilex seedlings was studied. Microclimate inside treeshelters containing seedlings was also measured along a typical summer day. Deep tillage increased germination and survival in comparison with untilled treatment. Temperature and leaf to air vapor pressure deficit was higher inside the treeshelters, specially in those without wholes, than outside. In spite of this fact, both treeshelter types, and particularIy those with lateral ventilation holes, exhibited a higher survival percentages than the control without treeshelter. Neither acorn seeding nor the removal of treeshelters in summer improved survival. significantly.
The following values have no corresponding Zotero field: periodical: II Congreso Forestal Español pub-location: Pamplona
Keywords: Acorn seeding; Holm oak; microclimate; Reforestation; Tillage

Seasonal and interannual occupation of a forest archipelago by insectivorous passerines - Tellería, J L; Santos, T (OIKOS, 1997)
The distribution of insectivorous passerines was studied in 31 fragments (0.1 to 350 ha) of a helm oak (Quercus ilex) Mediterranean forest archipelago in central Spain for two consecutive springs and winters (1988 to 1990). The study aimed to assess the role of forest size, abundance and other biological traits (nesting site and foraging substrata) of the species in their ability to occupy the fragments. The number of fragments occupied by the species (f(i)) was correlated to their abundance (d(i)) in spring and winter. Spring-to-winter changes of di correlated positively to changes off, due to the incidence of summer migrants but failed to show any significant pattern when restricted to species occurring in both seasons. The between-winter variations of cl, correlated positively with changes in f, while the between-spring changes of both parameters did not correlate, probably because of stronger effects of site fidelity on bird distribution in this period. Between-year persistence in the occupation of fragments was directly related to bird species abundance and, for a given abundance, persistence decreased in the smallest fragments. Hole-nesting species during the 1988 spring and the exploiters of scarce trees or foraging substrata during both winters showed an apparent restriction to colonize the smaller fragments due in parr to changes in habitat structure related to fragmentation. These results support the hypothesis that abundance is a good predictor of the ability of species to occupy and persist in fragments. However, abundance alone does not fully explain the processes that determine these occupancy patterns, since other traits related to the spatial scale of analysis and the suitability of fragments for each bird species are also involved.
APS
Keywords: abundance; biological traits; bird distribution; forest size; Holm oak; insectivorous passerines; mediterranean forest; Quercus ilex

Supervivencia y crecimiento de plántulas de encina en función de la intensidad de luz y la disponibilidad de agua - J.Ma, ESPELTA; RETANA, J; Riba, M (II Congreso Forestal Español, 1997)
The response of holm oak seedlings under a gradient of light and water av ail abilit y is analyzed. Seedling survival under all water levels decreased with increasing light. Conceming seedling morphology, both light and water availability changed biomass allocation to roots, stems and leaves, being light the most important source of variation
Keywords: Holm oak; light; Regeneration; Seedling; water

Effect of site quality and thinning management on the structure of holm oak forests in northeast Spain - Gracia, M; RETANA, J (Ann. For. Sci., 1996)
In the holm oak forests of NE Spain, the variability of thinning intensity, together with the great heterogeneity of site quality, due to the rough topography of the region, gives rise to important structural differences among stands. In this paper, we analyze the effect of site quality and thinning management on the structural heterogeneity of holm oak stands at the end of the cutting cycle in different areas of the Montseny and Les Guilleries massifs (NE Spain). These two factors influence the main structural variables of the stands in various ways. Height was used as an indicator of site quality, because it was relatively unaffected by thinning management, while density and total number of stems per stool were strongly affected. Mean tree diameter reflected the effect of both site quality and thinning. The type of forest management was found to be the most important factor determining forest structure. Site quality was a constraint of stand development, contributing in poor stands, to increased differences due to thinning management.
Keywords: Forest structure; Holm oak; Ouercus ilex; site quality; thinning

Effect of water stress on monoterpene emissions from young potted holm oak (Quercus ilex L.) trees - Bertin, N; Staudt, M (Oecologia, 1996)
We investigated the effects of a short period of water stress on monoterpene emissions from Quercus il- ex, a common oak species of the Mediterranean vegeta- tion and a strong emitter of monoterpenes. The experi- ment was carried out on two young saplings with a branch enclosure system under semi-controlled condi- tions. Under unstressed conditions, small qualitative (cis- [3-ocimene, trans-~3-ocimene, [3-caryophyllene and 1,8- cineol) and large quantitative (as much as 40% for the main compounds emitted) differences were observed be- tween the two apparently similar trees. Nevertheless these differences did not affect the short- and long-term responses to temperature and water stress. Daily courses of emissions and gas exchanges were similar before and after the stress. During the most severe stress, emissions were reduced by a factor of two orders of magnitude and the log-linear relationship between emissions and tem- perature no longer existed. Photosynthesis and transpira- tion rates decreased as soon as the soil started to dry, whereas monoterpene emissions slightly increased for few days and then dropped when the daily CO 2 balance approached zero. We concluded that under water stress monoterpene emissions were highly limited by monoter- pene synthesis resulting from a lack of carbon substrate and/or ATR After rewatering, both emissions and gas ex- changes recovered immediately, but to a level lower than the pre-stress level. These results have many implica- tions for monoterpene emission modelling in the Medi- terranean area, since the dry period generally extends from May to August. If our results are confirmed by field experiments, water stress could lead to a large overesti- mation of the emissions under summer conditions, when the algorithms based on light and temperature would give high emission rates.
Keywords: Holm oak; Mediterranean vegetation; monoterpene emission; Quercus ilex; water stress

Lixiviation as a tool for radionuclide fractionation in holm oak leaves - Tent, J; Rauret, G (JOURNAL OF RADIOANALYTICAL AND NUCLEAR CHEMISTRY-ARTICLES, 1996)
A sequential extraction scheme, using distilled water and chloroform : hexane(1:2) was applied in a study of radionuclide retention by helm oak leaves. To perform this study, holm oak leaves were contaminated by dry deposition using a thermogenerated radioactive aerosol containing Cs-134, Sr-85 and Ag-110m. The experimental parameters tested were: type and lime of shaking, number of successive extractions in each step, and the volume of extractans. From the results obtained, two schemes which give complementary information about radionuclide retention are proposed. The first scheme, using a single water extraction with mechanical shaking, allows us to define two fractions: the fraction removed by water, which is related to total radionuclide retention on leaf surfaces, and the residual fraction, which is associated with radionuclides incorporated into the leaves. The second scheme is based on a two-step extraction with manual shaking using water and chloroform :hexane, and permits us to distinguish among three fractions:the fraction removed by water(which is related to the radionuclide fraction easily leached by rain), the fraction removed by organic solvent (which is associated with the radionuclide fraction strongly retained on leaf surface), and the residual fraction, which may represent the absorbed radionuclide content. Since our objective was to study the retention of Cs-134, Sr-85 and Ag-110m, simultaneously, the experimental conditions chosen were a compromise of individual suitable conditions for each radionuclide.
APS
Keywords: Holm oak; radionuclide

Lixiviation as a tool for radionuclide fractionation in holm oak leaves - Tent, J.; Rauret, G. (JOURNAL OF RADIOANALYTICAL AND NUCLEAR CHEMISTRY-ARTICLES, 1996)
A sequential extraction scheme, using distilled water and chloroform : hexane(1:2) was applied in a study of radionuclide retention by helm oak leaves. To perform this study, holm oak leaves were contaminated by dry deposition using a thermogenerated radioactive aerosol containing Cs-134, Sr-85 and Ag-110m. The experimental parameters tested were: type and lime of shaking, number of successive extractions in each step, and the volume of extractans. From the results obtained, two schemes which give complementary information about radionuclide retention are proposed. The first scheme, using a single water extraction with mechanical shaking, allows us to define two fractions: the fraction removed by water, which is related to total radionuclide retention on leaf surfaces, and the residual fraction, which is associated with radionuclides incorporated into the leaves. The second scheme is based on a two-step extraction with manual shaking using water and chloroform :hexane, and permits us to distinguish among three fractions:the fraction removed by water(which is related to the radionuclide fraction easily leached by rain), the fraction removed by organic solvent (which is associated with the radionuclide fraction strongly retained on leaf surface), and the residual fraction, which may represent the absorbed radionuclide content. Since our objective was to study the retention of Cs-134, Sr-85 and Ag-110m, simultaneously, the experimental conditions chosen were a compromise of individual suitable conditions for each radionuclide.
APSAPSThe following values have no corresponding Zotero field: pub-location: PO BOX 245, H-1519 BUDAPEST, HUNGARY publisher: AKADEMIAI KIADO
Keywords: Holm oak; radionuclide

Assessment of sensitization to holm oak (Quercus ilex) pollen in the Mérida area (Spain) - Prados, M; Aragon, R; Carranco, M I; Martínez, a; Martínez, J (Allergy, 1995)
Sensitization to Quercus ilex(holm oak) was studied in 760 patients with clinical suspected sensitization to aeroallergens. Prick tests with commercial extracts of Q. ilex proved positive in 27 patients; none were monosonsitive. Nasal and conjunctival provocation tests and specific IgE (RAST) performed with Q. ilex extracts in these patients were negative in all hut one patient, who exhibited specific IgE: liter by RAST) of 7 PRU ml (class 3). We conclude that Q. ilex pollen, though obtained in considerable quantities by our collector, docs not cause allergies in our area.
Keywords: Holm oak; Mérida; Quercus ilex; sensitization

Dung Beetles (Coleoptera: Scarabaeidae, Geotrupidae) Attracted to Fresh Cattle Dung in Wooded and Open Pasture - Galante, Eduardo; MENA, JAVIER; LUMBRERAS, CARLOS (Environmental Entomology, 1995)
The biomass of dung beetles attracted to fresh cattle dung was studied in a Mediterranean holm oak pasture ecosystem with a continental Mediterranean climate (supramediterranean level). Results indicated a nonuniform biomass distribution of dung beetles throughout the year. Major peaks of species activity and biomass concentration of dung beetles occurred in open areas of the pasture in the spring followed by minor peaks in the fall. Beetle biomass in the open pasture was greater than that in the wooded pasture. The species of dung beetles comprising the greatest amount of biomass and the most important species available to destroy cattle dung pats in Mediterranean ecosystemswith a continental climate were Bubas bubalus Olivier, Onthophagus opacicollis d'Orbigny, Copris hispanus (L.), Copris lunaris (L.), and Onthophagus vacca (L.).
Keywords: biomass; dung beetles; Holm oak; Mediterranean ecosystem; pastureland

Dung Beetles (Coleoptera: Scarabaeidae, Geotrupidae) Attracted to Fresh Cattle Dung in Wooded and Open Pasture - Galante, Eduardo; MENA, JAVIER; LUMBRERAS, CARLOS (Environmental Entomology, 1995)
The biomass of dung beetles attracted to fresh cattle dung was studied in a Mediterranean holm oak pasture ecosystem with a continental Mediterranean climate (supramediterranean level). Results indicated a nonuniform biomass distribution of dung beetles throughout the year. Major peaks of species activity and biomass concentration of dung beetles occurred in open areas of the pasture in the spring followed by minor peaks in the fall. Beetle biomass in the open pasture was greater than that in the wooded pasture. The species of dung beetles comprising the greatest amount of biomass and the most important species available to destroy cattle dung pats in Mediterranean ecosystemswith a continental climate were Bubas bubalus Olivier, Onthophagus opacicollis d'Orbigny, Copris hispanus (L.), Copris lunaris (L.), and Onthophagus vacca (L.).
Keywords: biomass; dung beetles; Holm oak; Mediterranean ecosystem; pastureland

Patterns of seedling recruitment in West-Mediterranean Quercus ilex forest influenced by canopy development - Espelta, Josep Maria; Riba, Miquel; Javier, Retana (Journal of Vegetation Science, 1995)
Abstract. Quercus ilex (holm oak) coppice forests belong to the most representative communities in the western part of the Iberian Peninsula. Due to the high sprouting potential of holm oak after coppicing, the dynamics of recruitment of new individuals in existing populations has been largely overlooked. In these forests, the density of seedlings increases in old stands, as a result of the remarkable increase in the recruitment of 1-yr and 2-yr old seedlings, probably due to better environmental conditions for germination. Older seedlings show a tendency towards increasing survival under some degree of canopy closure, since their density appears to be higher just before complete canopy closure takes place. Nevertheless, the reduced growth of seedlings in older stands due to low light levels causes age distributions of holm oak seedlings to change drastically, with saplings older than 15 yr becoming very unusual in these stands. Therefore, a bottleneck of recruitment appears at this sapling stage and prevents vigorous regeneration just before thinning. Present conditions of genet density and management tend to prevent population renewal. Dynamics of the seedling bank reinforce the role of gap formation through small or large scale perturbations in population turnover.
Keywords: Holm oak; Regeneration; Seeder; Seedling dynamics; Sprouter; thinning

Deposition on holm oak leaf surfaces of accidentally released radionuclides - Rauret, G; Llauradó, M; Tent, J; Rigol, A; Alegre, L H; Utrillas, M J (Science of The Total Environment, 1994)
The retention of aerosols by canopies of holm oak trees in a typical Mediterranean forest is studied. Firstly, dry deposition is measured both under and outside the canopy during several months. No clear differences are observed either in the amount or in the chemical composition of the particles collected under and outside the canopy. Secondly, the leaf morphology and anatomy as well as the aerosol deposited onto the leaf surfaces are studied by scanning electron microscopy. Cuticle thickness is measured and differences are observed between young and old leaves. The distribution of aerosol particles over leaf surface is also established. Finally, the possible incorporation into leaves of a radioactive aerosol released in an accidental situation is studied, by means of a sequential extraction procedure using water and an organic solvent. From the results it can be deduced that neither the abiotic layer nor the cuticle play any important role in the retention of caesium. The studied radionuclides are mainly found in particulate form, soluble in water, or incorporated into leaves.
Keywords: Cuticle thickness; Holm oak; Leaf surface; Radionuclide deposition; Radionuclide incorporation; Sequential extraction

Deposition on holm oak leaf surfaces of accidentally released radionuclides - Rauret, G.; Llauradó, M.; Tent, J.; Rigol, A.; Alegre, L. H.; Utrillas, M. J. (Science of The Total Environment, 1994)
The retention of aerosols by canopies of holm oak trees in a typical Mediterranean forest is studied. Firstly, dry deposition is measured both under and outside the canopy during several months. No clear differences are observed either in the amount or in the chemical composition of the particles collected under and outside the canopy. Secondly, the leaf morphology and anatomy as well as the aerosol deposited onto the leaf surfaces are studied by scanning electron microscopy. Cuticle thickness is measured and differences are observed between young and old leaves. The distribution of aerosol particles over leaf surface is also established. Finally, the possible incorporation into leaves of a radioactive aerosol released in an accidental situation is studied, by means of a sequential extraction procedure using water and an organic solvent. From the results it can be deduced that neither the abiotic layer nor the cuticle play any important role in the retention of caesium. The studied radionuclides are mainly found in particulate form, soluble in water, or incorporated into leaves.
Keywords: Cuticle thickness; Holm oak; Leaf surface; Radionuclide deposition; Radionuclide incorporation; Sequential extraction

THE EUROPEAN PINE MARTEN MARTES-MARTES IN THE BALEARIC-ISLANDS, SPAIN - CLEVENGER, A. P. (MAMMAL REVIEW, 1993)
Between March and December 1990, a survey of Pine Marten Martes martes L. on the Balearic Islands of Minorca and Majorca was carried out. Pine Marten were found distributed over 55% of Minorca and occupied Aleppo Pine and Holm Oak forests, mediterranean shrublands and riparian/cliff habitats. In Majorca, Pine Marten were found on 48% of the island and three broad physiographic areas, the Sierra de Tramuntana, Sierra de Levant and the Massif de Randa. Droppings were collected along four designated routes during five bimonthly intervals in Minorca to describe the Pine Marten's differential use of habitat types. The upland/open pine forest had the highest use index while the Holm Oak forest had the lowest. The number of Pine Marten faeces collected was greatest during the months of July-August. The Balearic Island Pine Marten populations were once on the verge of extinction; however, protection during the last 20 years has enabled the species to recover throughout most of the forested habitats on both islands. Resource managers must carefully monitor the Pine Marten populations to provide the species and its habitat with adequate protection and management in the future.
APSAPSThe following values have no corresponding Zotero field: pub-location: OSNEY MEAD, OXFORD, OXON, ENGLAND OX2 0EL publisher: BLACKWELL SCIENCE LTD
Keywords: Aleppo pine; Balearic Islands; Holm oak; Martes martes L.

THE EUROPEAN PINE MARTEN MARTES-MARTES IN THE BALEARIC-ISLANDS, SPAIN - CLEVENGER, A P (MAMMAL REVIEW, 1993)
Between March and December 1990, a survey of Pine Marten Martes martes L. on the Balearic Islands of Minorca and Majorca was carried out. Pine Marten were found distributed over 55% of Minorca and occupied Aleppo Pine and Holm Oak forests, mediterranean shrublands and riparian/cliff habitats. In Majorca, Pine Marten were found on 48% of the island and three broad physiographic areas, the Sierra de Tramuntana, Sierra de Levant and the Massif de Randa. Droppings were collected along four designated routes during five bimonthly intervals in Minorca to describe the Pine Marten's differential use of habitat types. The upland/open pine forest had the highest use index while the Holm Oak forest had the lowest. The number of Pine Marten faeces collected was greatest during the months of July-August. The Balearic Island Pine Marten populations were once on the verge of extinction; however, protection during the last 20 years has enabled the species to recover throughout most of the forested habitats on both islands. Resource managers must carefully monitor the Pine Marten populations to provide the species and its habitat with adequate protection and management in the future.
APS
Keywords: Aleppo pine; Balearic Islands; Holm oak; Martes martes L.

Proanthocyanic polymorphism in holm oak (Quercus ilex L) in the Mediterranean region of France - Lebreton, P; Barbero, M; Nader, S (Ann. For. Sci., 1993)
We studied the proanthocyanic diversity of holm oak in France. The percentage of prodelphinidin remains constant for each individual tree, independent of age or location of the leaves. By contrast, this content can be significantly different between trees within the same population. An in-depth analysis of a Languedocian population showed a good relationship between observed and predicted sample structure, according to the hypothesis of 2 alleles, prodelphinidin 'weak' and 'strong', respectively, governing the biosynthesis of this polyphenol. We have probably observed a biochemical polymorphism comparable to that previously demonstrated for several coniferous species.
Keywords: Holm oak; Polymorphism; prodelphinidin

SUPERVIVENCIA DE PLANTULAS DE PINO CARRASCA (PINUS HALEPENSIS) y ENCINA (QUERCUS ILEX) EN BOSQUE MIXTOS DE AMBAS ESPECIES - ESPELTA, J M; RETANA, J; Gené, C; Riba, M (Congreso Forestal Español, Lourizán - Pontevedra. 1993, 1993)
In this paper, survival of holm oak and Aleppo pine seedlings in holm oak stands, Aleppo pine stands and mixed stands, both in cut and uncut plots, is analized. Survival of holm oak seedlings in uncut plots is greater than that of Aleppo pine seedlings in the three types of forest considered. Mortality of seedlings of both species in 9ut plots is considerably smaller than that of uncut plots. K.W.:
Keywords: Aleppo pine; Holm oak; mixed forest; Seedling; survival curve

Growth and yield of young Quercus ilex coppice stands in the Tafferte forest (Morocco) - Khatouri, M (Plant Ecology, 1992)
The coppice method is the silvicultural system commonly applied to Quercus ilex (holm oak) forests for the production of firewood and charcoal. Although the holm oak is the species that covers the largest area in Morocco (1400000 hectares), little is known about its growth and yield. The objective of this study is to quantify the stand growth and yield of young coppice holm oak stands in the Tafferete for- est in the eastern part of the Middle Atlas (Morocco). Equations relating dominant height to age, and basal area, volume, and number of trees to dominant height were developed and used to derive young holm oak coppice yield estimates. The growth and yield information developed in this study may have a greater utility in defining cul- tural measures that should be applied in the early stage of holm-oak coppice stands.
Keywords: Diameter Distribution; Growth Curves; Holm oak; middle atlas; production

HABITAT PREFERENCE OF SPANISH IBEX AND OTHER UNGULATES IN SIERRAS DE CAZORLA Y SEGURA (SPAIN) - ESCOS, J.; Alados, C. L. (MAMMALIA, 1992)
Studied the habitat preference in Autumn and Spring periods of Spanish ibex (Capra pyrenaica), fallow deer (Dama dama) and red deer (Cervus elaphus) in the Sierras de Cazorla y Segura Park (Spain). Spanish ibex occupied most altitude range studied, especially highest parts and avoiding areas below 800 m, red deer selected lowest elevations between 700 to 1100 m and fallow deer (between 1200-1600 m) occupied an intermediate annual altitudinal range. All the ungulates studied showed, except the red deer populations, a descent of altitudinal levels in the Spring period. Ibex used more covered areas specially females and young in Spring period, fallow deer occupied open habitats and red deer preferred holm-oak woods. In general terms the rut occurred in more open areas while in the birth season, females and young especially occupied covered areas. According to the overlap index (Pianka 1973) ibex with fallow deer could get a high risk of competition, while Spanish ibex and red deer, the only endemic species show the lowest level of overlapping on the resources studied. Segregation of the sexes studied in different habitats was observed. In Autumn, Spanish ibex and fallow deer showed a tendency to occupy sunny areas at dawn and dusk and this tendency occurred in red deer only at dawn but not at dusk. However in Spring, Spanish ibex, fallow and red deer occupied sunny slopes at dusk but only fallow deer do so at dawn.
The following values have no corresponding Zotero field: pub-location: 55 RUE DE BUFFON, 75005 PARIS, FRANCE publisher: MUSEUM NAT HIST NATURELLE
Keywords: APS; Capra pyrenaica; cervus elaphus; Dama dama; habitat prefference; Holm oak; Spain; ungulates

Litter dynamics in post-fire successional forests of Quercus ilex - FERRAN, A.; Vallejo, V. R. (Plant Ecology, 1992)
Forest floor regeneration after fire in a holm oak forest was studied in a chronosequence in Catalonia (NE Spain). The sampled area represented situations of high fire disturbance because of the frequency of wildfires and the high impact of erosive processes. Forest floor bulk samples from the L, F and H layers were taken in 5 burned plots, aging from 0 to 35 years. They were analyzed for dry standing weight, and organic carbon and N content. Plant cover reached almost 100°o two years after the fire. During the first 20 years, shrubs and herbs had the highest surface covering, and thereafter, holm oaks became dominant. Holm oak litterfall stabilized by the fourth year after burning. The major shrub species which were present in the chronosequence had two different patterns with respect to nitrogen: 1) a low litter C/N ratio (i.e. nitrogen fixing species); 2) a high litter C/N ratio. The litter decay coefficients were relatively high, allowing for a rapid structuration and formation of the L and F layers after the fire. Indeed, 95 ° o of the maximum steady standing weight accumulates in 8-9 years. The pattern of cover in the different strata influenced the lateral distribution and variable accumulation of the forest floor layers and determined different turnover rates.
Keywords: C/N ratio; Decay coefficient; Holm oak; mediterranean forest; plant regeneration

COLOLEJEUNEA-MINUTISSIMA (SM) SCHIFFN IN THE HOLM OAK GROVE OF PORT-CROS ISLAND (ILES DHYERES, VAR, FRANCE) - Hebrard, J P; ROUX, C (NOVA HEDWIGIA, 1991)
Discovery of Cololejeunea minutissima (Sm.) Schiffn. on Quercus ilex trunks within the holm-oak forest on Port-Cros island (departement Var). Bionomic, chorological and ecological remarks on the species.
APS
Keywords: Cololejeunea minutissima; Holm oak; Quercus ilex

Thermal decomposition of wood in oxidizing atmosphere. A kinetic study from non-isothermal TG experiments - Cordero, T; Rodriguez-Maroto, J M (Thermochimica acta, 1991)
The kinetics of thermal decomposition of four wood species in oxygen-bearing atmo- spheres of 5, 10 and 20% molar Oz concentrations have been studied from temperature-pro- grammed experiments carried out at 5, 10 and 20 K mm ’ -* heating rate. Devolatihzation as weII as combustion of the reaminin g solid have been considered to analyze the weight loss curves. The homogeneous volume reaction (VR) model has been used to describe devolatihza- tion, whereas for solid combustion the grain model has been also checked. A two-stage approach has been used to fit the conversion-time curves and to derive the corresponding apparent kinetic parameters. The VR/VR (pyrolysis/combustion) combination provided a better description of the experimental (~-1 curves than the VR/grain combination. Hohn oak and cork oak showed very close reactivities, whereas some differences were observed for aleppo pine and eucalyptus.
Keywords: Aleppo pine; combustion (voyant); Cork oak; EUCALYPTUS; Holm oak; Kinetic model; pyrolysis; Wood

CO2 and steam gasification reactions of a charcoal from holm-oak wood. KINETIC AND TEXTURAL CHARACTERIZATION - Valenzuela Calahorro, C; Bernalte García, M J; Serrano Gómez, V; Bernalte García, A (BIOMASS FOR ENERGY AND INDUSTRY: 5th E.C. Conference, 1990)
In this work are shown the kinetic results of carbon dioxide and steam gasification reactions of a charcoal from holm-oak wood and the evolution of some textural parameters (BET surface area, micropore and mesopore volume) of several activated carbons prepared by such reactions
APS
Keywords: activated carbon; Carbon dioxide; charcoal; Holm oak; kinetic; steam gasification

Precipitation, throughfall, soil solution and streamwater chemistry in a holm-oak (Quercus ilex) forest - Rodà, Ferran; Avila, Anna; Bonilla, David; Rodà, Ferran (Journal of Hydrology, 1990)
Bulk precipitation, throughfall, soil solution at 20 and 40 cm depths, and stream water were monitored for 2–4 years in a holm-oak forest on schists in the Montseny Mountains (NE Spain). Bulk precipitation was mildly acidic, with Ca2+ and SO2−4 as dominant ions. Canopy interactions produced a throughfall less acidic than bulk precipitation and enriched in all other ions. Large amounts of K+ were leached from the canopy. Magnesium in net throughfall behaved similarly to K+, and it is concluded that leaching makes a major contribution to Mg2+ enrichment beneath the canopy. Judging from the moderate increase of Na+ and Ca2+ in throughfall, dry deposition rates for both marine and continental aerosols were low in the studied stand, probably because of its sheltered topographic position within a well-vegetated massif, coupled with moderate tree height and low canopy roughness. Soil solution in the mineral soil was less acidic than throughfall. In common with most temperate forests, SO2−4 was the dominant mobile anion in the soil water, being largely accompanied by Ca2+. Potassium and NO−3 were depleted within the soil water with respect to throughfall, probably owing to biological uptake and cation exchange, and incorporation of K+ into clay lattices. Subsurface flow dominated the hydrology of the small forested catchment studied. Stream water was basic and rich in bicarbonate. Its chemistry revealed fast rates of weathering of sodium- and magnesium-bearing silicates (mainly albite and chlorite, respectively). Soil respiration and silicate hydrolysis resulted in HCO−3 being the dominant mobile anion in stream water. Calcium to chloride ratios were similar in bulk precipitation and in stream water, indicating that Ca2+ release from weathering has been counteracted by plant uptake. Nutrient uptake by this aggrading forest strongly influences the solution dynamics of K+, NO3 and Ca2+. It is concluded that: (1) this forest does not currently receive acidic atmospheric deposition; (2) the neutralization capacity of the soil-bedrock system is quite high; (3) biotic regulation and silicate weathering are the major processes shaping the solution biogeochemistry in this Mediterranean forest ecosystem.
Keywords: Canopy; chemistry (voyant); Holm oak; Montseny mountains; Precipitation; soil solution; stream water; throughfall

THE TIMING OF BREEDING AND CLUTCH SIZE OF BLUE TITS (PARUS-CAERULEUS) IN AN EVERGREEN HOLM OAK HABITAT IN SOUTHERN SPAIN - ISENMANN, P; ALES, E; MORENO, O (REVUE D ECOLOGIE-LA TERRE ET LA VIE, 1990)
APS
Keywords: blur tits; clutch size; Holm oak; Parus cearuleus; Spain

A kinetic study of holm oak wood pyrolysis from dynamic and isothermal TG experiments - Cordero, T; Garcia, F; Rodriguez, J J (Thermochimica acta, 1989)
The kinetics of holm oak wood thermal decomposition in a nitrogen atmosphere have been studied using dynamic and isothermal TG experiments. A number of different kinetic models are examined. Discrimination between the first order, second order and spherical symmetry boundary surface reaction models is difficult with the dynamic TG experiments. The isothermal weight loss curves obtained are best described by a first order rate equation.
Keywords: heating rates; Holm oak; isothermal experiment; Kinetic model; pyrolysis (voyant); Wood

PYROLYSIS OF HOLM OAK AND OLIVE WOOD - Figueiredo, J L (International Conference on Biomass for Energy and Industry, 1989)
The pyrolysis of olive and holm-oak wood to produce charcoal and fuel gas was studied in the temperature range from 3 00 to 9 00°C. The charcoals were characterized by proximate and ultimate analyses, and the gases were analyzed chromatographycally The fised carbon content of the charcoal increased with temperature up to 600-700°C and then remained essentially constant. The gases produced were mainly CO, CO , H and CH . The composition of the pyrolysis gas produced at each temperature was determined, and its heating value was calculated. Taking into consideration the quality of the charcoal and the heating value of the gases produced, it can be concluded that the optimal pyrolysis temperature is 600'C.
APS
Keywords: charcoal production; fuel gas; Holm oak; olive; pyrolysis

Melophia ophiospora Lev. Sacc., mutatis characteribus, a phellophagic fungus on cork-oak - Speer, E O (Mycotaxon, 1984)
APS
Keywords: Fungus; Holm oak; Pragas e doencas - Melophia ophiospora

Sui Limiti Altimetrici Dei Consorzi Rupestri Di Leccio in Garfagnana - Arrigoni, Pier Virgilio (Giornale botanico italiano, 1956)
Summary One of the most characteristic species of the present Mediterranean vegetation, the holm-oak, still presents in the Appennines, after the alternate glacial periods, relict stations, separated and disjointed, strictly bound to the rocky places. The Author takes the examination of the altimetrical limits of the holm-oak in Garfagnana (Tuscany), in the valleys of Turrite Secca and Fegana, as a starting point to take into consideration the value and the floristic-oecological aspects of these rocky relicts. After a climatic and geomorphologic classification of the examined places, the distribution of the holm-oak in the aforesaid valleys is minutely described. The historical examination shows a derivation of the present plant-communities, rocky and relict, from the dispersion of a presumable anathermic mountain forest, referable to the period of the Quercetum mixtum, rather than to the ancient tertiary, thermophilous and orophilous, Mediterranean forest. The permanence of the holm-oak in the submontane and mountain stations is strictly bound to their peculiar oecology and its specific temperament. The rocky stations, at least those examined in Garfagnana, are remarkably arid and thermically continental, especially those exposed to the south and south-west. Their aridity, however, helps to lessen the dangers of the frost. The holm-oak can live there in virtue of its tolerance and biological plasticity. To the south it reaches the most elevated heights owing to the protection from cold winds and owing to its greater thermic availability. A peculiar attention is given to the dynamics, in time and space, of the floral-physiognomical groups: dynamics which has its impulse in the unceasing instability of the rocky micro-places. Some botanic observation, made in different floral districts, in different conditions of positions, altitude and nature of the substratum, aim at representing the floral aspects of the examined Quercus Ilex-stations. The flora is constituted with entities fit (preadapted) for the rocky places and with species supplied with remarkable qualities of adaptation. Through the comparisons of the biological spectra, it appears the great fitness of the Chamephytes to the harsh rocky places. Among the few Mediterranean species able to follow the holm-oak in the rocky localization it is worth mentioning, above all, the Juniperus phoenicea L., species typically of the littoral, never noticed in Tuscany at such elevated heights as those which have been noticed, as it appears in this work, in the Apuane Alps (till 1200 metres).
doi: 10.1080/11263505609431629
Keywords: Holm oak; Plasticity (PG); Quercetum mixtum; rocky relicts; tuscany